CEHP (CEHP)
Soutenir et accompagner les organisations dans une saine gestion du harcèlement psychologique au travail
Keywords: Bibliographie; Nettoyer

* Prud'homme c. Prud'homme, 2002 CSC 85 (CanLII), [2002] 4 RCS 663
Keywords: Bibliographie; Nettoyer

“#UsToo”: Empowerment and Protectionism in Responses to Sexual Abuse of Women with Intellectual Disabilities - Boux, Holly Jeanine (Berkeley Journal of Gender, Law & Justice, 2022)
Keywords: Bibliographie; Nettoyer

Sex Worker Resistance in the Neoliberal Creative City: An auto/ethnography - Tigchelaar, Alex (Anti-Trafficking Review, 2019)
Sex workers are subjects of intrigue in urban and creative economies. Tours of active, deteriorating, or defunct red-light districts draw thousands of tourists every year in multiple municipalities around the world. When cities celebrate significant anniversaries in their histories, local sex worker narratives are often included in arts-based public offerings. When sex workers take up urban space in their day-to-day lives, however, they are criminalised. Urban developers often view sex workers as existing serviceably only as legend. A history of sex work will add allure to an up-and-coming neighbourhood, lending purpose to its reformation into a more appropriately productive space, but the material presence of sex workers in these neighbourhoods is seen as a threat to community wellbeing and property values. This paper considers how sex workers, continuously displaced from environments they have carved out as workspaces, may use the arts to draw attention to these ongoing contradictions. It investigates how sex workers may make visible the idiosyncratic state of providing vitality to a city’s history while simultaneously being excluded from its living present. Most critically, it suggests ways in which sex workers may encourage those involved as producers and consumers of neoliberal urban revitalisation projects to connect these often fatal paradoxes to the laws that criminalise their labour.
Keywords: Bibliographie; Nettoyer

Québec, un modèle de « safe space » ? - Léger, Souen (Livres Hebdo, 2021)
Face au #metoo qui a secoué l'édition québécoise à l'été 2020, le milieu littéraire a posé des premiers jalons garantissant des rapports exempts de harcèlement et de violences sexuelles. Une réponse rapide, organisée, qui témoigne de la longueur d'avance prise par le Québec sur les enjeux liés au féminisme et à l'inclusion. De quoi séduire les autrices, françaises notamment. Et donner des idées à la France ?
Keywords: Bibliographie; Nettoyer

Vague de dénonciations : un groupe de soutien est créé dans le milieu littéraire - Larouche, Katy (Radio-Canada, 2020)
Keywords: Bibliographie; Nettoyer

Des violences sexuelles et des abus de pouvoir dénoncés dans le milieu littéraire - Bourel, Fanny (Radio-Canada, 2020)
Un groupe de 300 personnes s’est créé pour que les victimes témoignent et pour exprimer des revendications.
Keywords: Bibliographie; Nettoyer

Comment écrire le viol ? - Clément, Éric (La Presse+, 2018)
Le sujet est délicat. Tellement que plusieurs personnes contactées ont refusé de se prononcer sur cette nouvelle prise de conscience qui découle des mouvements #moiaussi et #agressionnondénoncée. Les romanciers doivent-ils s’autocensurer pour respecter une nou
Keywords: Bibliographie; Nettoyer

Code of Silence: A call to action to address and prevent abuse in dance communities - Forcier, Marie France (The Dance Current, 2017)
Keywords: Bibliographie; Nettoyer

Agression sexuelle : L'écrivain Maxime Roussy remis en liberté - Helmlinger, Julien (ActuaLitté, 2013)
Keywords: Bibliographie; Nettoyer

Politique sur le respect des personnes, la prévention et l’intervention en matière de harcèlement - Université du Québec à Montréal (2024)
Keywords: Bibliographie; Nettoyer

LGBTQ2+ Inclusion in Canadian museums - Canadian Museums Association
Keywords: Bibliographie; Nettoyer

Working girl: on selling art and selling sex - Giovannitti, Sophia (Verso, 2023)
"Giovannitti argues that if we delve into our anxieties around art and sex, we can find new ways to live and spaces of freedom"--
Keywords: Bibliographie; Nettoyer

La musique québécoise à l'ère de #MeToo - Caza, Pierre-Etienne (Actualités UQÀM, 2020)
La musicologue Vanessa Blais-Tremblay analyse l’évolution des chansons évoquant des violences à caractère sexuel.
Keywords: Bibliographie; Nettoyer

Naviguer les attentes genrées de la communauté de danse swing de Montréal - Batty, Megan (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Keywords: Bibliographie; Nettoyer

L’opéra, un monde professionnel hanté par les violences de genre - Buscatto, Marie; Helbert, Soline; Roharik, Ionela (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Le 19 août 2020, la soprano Chloé Briot dénonce dans La Lettre du Musicien des agressions sexuelles répétées portées par un collègue chanteur lors de la production de l’opéra L’inondation. Faute d’avoir été entendue et défendue par sa direction, elle annonce encore avoir porté plainte devant la justice française dès le mois de mars de la même année et vouloir ainsi « en finir avec la loi du silence ». Pourquoi l’artiste lyrique n’a-t-elle pas été entendue à plusieurs reprises malgré ses plaintes auprès de ses collègues et de la production ? Dans quelle mesure cette agression sexuelle est-elle symptomatique d’un mode de fonctionnement sexiste plus large du monde de l’opéra français ? Peut-on parler effectivement d’une « loi du silence » dénoncée par la chanteuse ? Si oui, que risquent ceux et celles qui dénonceraient des faits sexistes et des violences sexuelles ?
Keywords: Bibliographie; Nettoyer

#metoo 2.0 to #meNOmore: Analysing Western Reporting About Sexual Violence in the Music Industry - Baker, Andrea; Williams, Katrina; Rodrigues, Usha M. (Journalism Practice, 2020)
In October 2017, #metoo 2.0 reinforces the gendered sexual violence in the creative sector [Marghitu, 2018. “It’s Just art: Auteur Apologism in the Post-Weinstein era”, Feminist Media Studies, 18(93): 491–494] Building on this movement, on 11 November that year, 2912 women “testified about the situation in the Swedish music industry”, signing an open letter condemning sexual violence [Nyheter, 2017. “2192 Women in the Swedish Music Industry Behind Appeal Against Sexism.” Dagens Nyheter, November 17. https://www.dn.se/kultur-noje/2192-women-in-the-swedish-music-industry-behind-appeal-against-sexism/]. After the Swedish initiative, on 12 December 2017, the #meNOmore hashtag was established by 1000 women who signed an open letter to the Australian music industry speaking out against similar behaviour [Whyte, 2017a. “Artists Speak Out Against Sexual Harassment in the Music Industry.” AM – ABC Radio, December 13. https://www.abc.net.au/radio/programs/am/sexual-harassment-in-the-music-industry/9253956]. Using a content analysis framework, this study examines the media framing of 26 stories about #meNOmore by the Western press from 22 November 2017 (height of the Swedish campaign) to 21 December 2017 (a week after the hashtag surfaced in Australia). Research from journalism studies and musicology highlights that sexual violence is historically engrained in the media and music industries. However, findings from our study of the first month’s coverage of the #meNOmore content analysis in 2017 reveal that media reports about women and sexual violence were framed around addressing gender inequality and systemic structural issues in the music industry. This raises the question, has the media has turned a corner when covering sexual violence in the post #metoo era?
Keywords: Bibliographie; Nettoyer

Sexual Harassment and Violence at Music Concerts and Festivals - Heen, Miliaikeala Sj.; Lieberman, Joel D. (Center for Crime and Justice Policy, 2018)
Keywords: Bibliographie; Nettoyer

Morinom - Office québécois de la langue française (Grand dictionnaire terminologique, 2022)
Prénom qui a été donné à une personne à sa naissance, mais que celle-ci ne souhaite plus qu'on emploie pour la désigner.
Keywords: Bibliographie; Nettoyer

Impact de la violence sexuelle sur la santé mentale - Centre d’Innovation en Santé Mentale sur les campus (2024)
Keywords: Bibliographie; Nettoyer

intersectionnalité - Office québécois de la langue française (Grand dictionnaire terminologique, 2019)
Cumul de différentes formes de domination ou de discrimination vécues par une personne, fondées notamment sur sa race, son sexe, son âge, sa religion, son orientation sexuelle, sa classe sociale ou ses capacités physiques, qui entraîne une augmentation des préjudices subis.
Keywords: Bibliographie; Nettoyer

Raport de recherche de l'enquête pièces : violences sexuelles en milieu collégial au Québec - Bergeron, Manon; Gagnon, Audréanne; Blackburn, Marie-Ève; M-Lavoie, Dominique; Paré, Caroline; Roy, Sophie; Szabo, Andrea; Bourget, Claudie (Chaire de recherche sur les violences sexistes et sexuelles en milieu d’enseignement supérieur, Université du Québec à Montréal, 2020)
Keywords: Bibliographie; Nettoyer

La relation de pouvoir entre un professeur et ses étudiantes - Radio-Canada (Tout un matin, 2022)
Tout un matin | L'ex-professeur de littérature Samuel Archibald aurait commis des « violences à caractère sexuel » et du « harcèlement sexuel » envers deux étudiantes avec lesquelles il était en situation d'autorité en tant que directeur de maîtrise. Le lien d'emploi entre l'auteur et l'Université du Québec à Montréal (UQAM) aurait été rompu l'année dernière. Au micro de Tout un matin, Rachel Chagnon, professeure au Département des sciences juridiques de l'UQAM, définit ce qu'est une relation de pouvoir entre un enseignant et un étudiant (ce sont majoritairement des femmes), principe qui se trouve au cœur de la politique de l'université pour prévenir et combattre les violences à caractère sexuel.
Keywords: Bibliographie; Nettoyer

Californie: Un professeur de musique de McGill poursuivi pour agression sexuelle - Siag, Jean (La Presse, 2024)
Un professeur de musique de l’Université McGill est poursuivi au civil aux États-Unis par deux anciennes étudiantes disant avoir été agressées sexuellement à l’époque où il enseignait en Californie. Des allégations que le professeur nie vigoureusement.
Keywords: Bibliographie; Nettoyer

Université de Montréal: briser l'omerta - Elkouri, Rima (La Presse, 2018)
Keywords: Bibliographie; Nettoyer

Dénoncer le harcèlement dans le milieu de l'improvisation - Radio-Canada (D'Est en Est, 2020)
Keywords: Bibliographie; Nettoyer

Représentation du viol en littérature: pour dire quoi? - Boisclair, Isabelle (Le Devoir, 2018)
Keywords: Bibliographie; Nettoyer

Danse #WeToo - Ferron, Geneviève C. (Regroupement québécois de la danse, 2018)
// English version Depuis l’émergence du mouvement #metoo en octobre dernier, plusieurs femmes artistes du Québec ont pris la parole pour dénoncer le harcèlement, l’intimidation et les abus dont elles ont été victimes ou témoins dans le cadre de leur […]
Keywords: Bibliographie; Nettoyer

L'intimidation et la cyberintimidation au Québec: portrait à partir de l'Étude québécoise sur les rapports sociaux dans un contexte scolaire, de travail et dans la communauté 2022 - Aranibar Zeballos, Daniela; Paquette, Jesseca (Institut de la statistique du Québec, 2024)
Keywords: Bibliographie; Nettoyer

Consultations publiques sur le harcèlement et la violence sexuelle en milieu de travail: ce que nous avons entendu - Emploi et Développpement social Canada (Gouvernement du Canada, 2017)
Keywords: Bibliographie; Nettoyer

Entente collective entre l'Union des artistes et l'Association québécoise de la production médiatique (Artistes interprètes) (2020)
Keywords: Bibliographie; Nettoyer

Une victime de Claude Jutra témoigne: des attouchements dès 6 ans - Pilon-Larose, Hugo (La Presse, 2016)
Keywords: Bibliographie; Nettoyer

Edgar Fruitier est libre après moins d’un mois de prison - Radio-Canada (Radio-Canada, 2022)
Son risque de récidive est jugé faible en raison de son état physique et mental.
Keywords: Bibliographie; Nettoyer

Tomber : Michel Brûlé - Radio-Canada
Keywords: Bibliographie; Nettoyer

Michel Venne devra finalement prendre le chemin de la prison - Marin, Stéphanie (Le Devoir, 2024)
Keywords: Bibliographie; Nettoyer

Jian Ghomeshi est acquitté - Radio-Canada (Radio-Canada, 2016)
Jian Ghomeshi est acquitté de toutes les accusations qui pesaient contre lui. Le juge William B. Horkins a rendu sa décision, jeudi matin, à Toronto.
Keywords: Bibliographie; Nettoyer

Sans consentement : trente scandales sexuels qui ont changé le Québec - Morin, Michel (2024)
Depuis l'arrivée de #MoiAussi et des autres mouvements de libération de la parole, on a assisté au Québec à une succession de scandales sexuels impliquant des personnalités publiques, figures respectées et influentes qui avaient abusé de leur pouvoir, parfois des décennies durant. Michel Morin fait un pas de côté pour revisiter ces histoires encore sensibles, en portant une attention particulière à leur traitement médiatique. Avocat de formation, il se penche aussi sur le fonctionnement du système judiciaire et son impact sur le processus de dénonciation. Sans s'ériger en juge, l'auteur laisse parler les faits, bien souvent accablants, dans un essai qui permet de prendre la mesure de ce qui a été trop longtemps ignoré, voire toléré, et du chemin qui reste à parcourir.
Keywords: Bibliographie; Nettoyer

Stratégie en matière de justice autochtone : Ce que nous avons appris Phase 1 de la mobilisation dirigée par le ministère de la Justice Canada - Ministère de la justice Canada (2023)
Keywords: Bibliographie; Nettoyer

Justice réparatrice en matière de violence conjugale : Enjeux et recommandations - Conseil du statut de la femme (2024)
Keywords: Bibliographie; Nettoyer

L'artiste et son oeuvre - McEwen, Jérémie (2022)
Keywords: Bibliographie; Nettoyer

Dénoncé en ligne, Yann Perreau est lui aussi largué par sa maison de disques - Radio-Canada (Radio-Canada, 2022)
Keywords: Bibliographie; Nettoyer

Le jour où Éric Salvail est tombé - Bourgault-Côté, Guillaume (Le Devoir, 2020)
Keywords: Bibliographie; Nettoyer

Prix Artis : le retrait de la nomination de Maripier Morin confirmé par TVA | Radio-Canada - Radio-Canada (Radio-Canada, 2021)
Keywords: Bibliographie; Nettoyer

Simple Plan renvoie son bassiste de tournée suite à des allégations d’inconduites sexuelles contre lui - Bibeault, Matt (99scenes, 2020)
C’est la firme de management de Simple Plan, Coalition Music, qui a confirmé la nouvelle. Chady Awad avait justement remplacé David Desrosiers lorsque ce dernier avait pris une pause de SP pour traiter sa dépression de 2017 à 2019. Awad était également photographe et vidéaste pour Simple Plan. Simple Plan a mis fin à sa... View Article
Keywords: Bibliographie; Nettoyer

Philippe Bond était déjà sur des listes noires - Bélanger, Cédric (Le Journal de Québec, 2022)
L'humoriste Philippe Bond était déjà depuis plusieurs années sur la liste noire de grandes organisations culturelles.
Keywords: Bibliographie; Nettoyer

Politique visant à prévenir et combattre les violences à caractère sexuel - École nationale de théâtre du Canada (2022)
Keywords: Bibliographie; Nettoyer

Dis Son Nom - Liste officielle des abuseuses et abuseurs présumés du Québec
Keywords: Bibliographie; Nettoyer

Mettre fin au harcèlement sexuel dans le cadre du travail : Se donner les moyens pour agir - Cox, Rachel; Gesualdi-Fecteau, Dalia; Laflamme, Anne-Marie (Comité chargé d'analyser les recours en matière de harcèlement sexuel et d'agressions sexuelles au travail, 2023)
Keywords: Bibliographie; Nettoyer

Safia Nolin répond à la haine par la musique - Caillou, Annabelle (Le Devoir, 2024)
Se gardant de tout révéler, l’artiste explique qu’elle sera sur scène avec pour seules armes sa guitare et sa voix.
Keywords: Bibliographie; Nettoyer

Poursuite intentée par Gilbert Rozon: La requête de Julie Snyder et Pénélope McQuade rejetée en appel - Morin-Martel, Florence (La Presse, 2022)
La poursuite de Gilbert Rozon réclamant 450 000 $ à Julie Snyder et Pénélope McQuade pour diffamation ira de l’avant. La requête des deux animatrices visant à mettre fin aux procédures, qui relèvent « d’une poursuite-bâillon », selon elles, a été déboutée en Cour d’appel, vendredi.
Keywords: Bibliographie; Nettoyer

De nouveaux gestes déplacés de musiciens dénoncés - Papineau, Philippe (2020)
Keywords: Bibliographie; Nettoyer

Prendre soin de sa santé psychologique en culture avec Florence Morin-Parent, psychologue (Le répondeur de l'industrie musicale, 2024)
Keywords: Bibliographie; Nettoyer

Vague de suicides chez les artisans de la scène: Quand le rideau tombe à jamais - Blais-Poulin, Charles-Éric; Groguhé, Marissa (La Presse, 2022)
Keywords: Bibliographie; Nettoyer

Comment aider un·e ami·e qui a eu des comportements abusifs par le passé (et qui a changé depuis) ? - Thom, Kai Cheng (Nous faire justice : Reader sur le viol et les ripostes extra-pénales, 2019)
Keywords: Bibliographie; Dans le rapport; Nettoyer

Étude sur l’expérience des adultes ayant reçu des services dans le cadre d’un processus judiciaire : Dossiers judiciarisés entre juillet 2020 et juin 2022 au Québec concernant une infraction commise dans un contexte de violence conjugale ou sexuelle - Institut de la statistique du Québec (2023)
Keywords: Bibliographie; Nettoyer

Farinelli - Corbiau, Gérard (1994)
Keywords: Bibliographie; Nettoyer

Orchestres symphoniques: une parité favorisée par un processus à l'aveugle - Larochelle, Samuel (La Presse, 2018)
Femmes et hommes côte à côte dans les orchestres symphonique d'ici. La question de parité est souvent lié au processus de sélection à l'aveugle des musiciens, une façon de faire qui permet de mettre de l'avant le talent, et ce, peu importe le sexe des artistes.
Keywords: Bibliographie; Nettoyer

Intermittents du spectacle - France Travail (2024)
Keywords: Bibliographie; Nettoyer

Code de conduite - Salon du livre de Montréal
Keywords: Bibliographie; Coffre à outils; Nettoyer

Différences et inégalités de genre dans la musique au Québec (DIG! Musique Québec)
DIG! est un réseau interdisciplinaire et intersectoriel visant la mutualisation des savoirs liés aux différences et aux inégalités de genre dans la musique au Québec.
Keywords: Bibliographie; Nettoyer

Cultive, la plateforme du développement professionnel en culture (Cultive, 2024)
Plateforme qui rassemble les offres de formation, les outils et les références pour le développement de votre carrière en culture au Québec.
Keywords: Bibliographie; Nettoyer

Backlash: the undeclared war against American women - Faludi, Susan (Anchor books, 1991)
Keywords: Bibliographie; Nettoyer

Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance - Risner, Doug; Watson, Beccy (Springer International Publishing, 2022)
Keywords: Bibliographie; Nettoyer

Femmes et jazz dans le Québec de l’entre-deux-guerres : entre le récit historique, les archives et le passé - Blais-Tremblay, Vanessa (Les Cahiers de la Société québécoise de recherche en musique, 2017)
This article contextualizes some of the roles that women played in Montreal’s interwar jazz scene. The archives testify to the importance of pianists such as Vera Guilaroff and Ilene Bourne, piano teacher Daisy Peterson Sweeney, dance teachers Olga Spencer Foderingham and Ethel Bruneau, as well as black women performers on the variety stage in the development of Canada’s most thriving jazz scene in the first half of the twentieth century. This article explains why women were drawn to these particular performance spaces (piano, teaching, theatrical dance) and documents the historiographical processes that have led to their marginalization from the historical record.
Keywords: Bibliographie; Nettoyer

Salut ça va ? Dialoguer pour prévenir les violences sexuelles - Clermont-Dion, Léa (Cardinal, 2024)
Dans cet essai coup-de-poing, Léa Clermont-Dion s’adresse d’abord aux adolescents et aux jeunes adultes, à leurs parents et à leurs professeur.es, pour ouvrir la discussion sur les violences à caractère sexuel. Son but : éduquer et sensibiliser pour parvenir à des rapports humains respectueux et égalitaires, toujours en évitant de blâmer qui que ce soit. L’autrice vulgarise les concepts de consentement, de culture du viol, de masculinité toxique et explore la portée du mouvement #MeToo. Elle échange aussi avec des acteurs-clé du monde du sport, dont Laurent Duvernay-Tardif, ainsi qu’avec des intervenants du système de justice et recueille de bouleversants témoignages de victimes.
Keywords: Bibliographie; Nettoyer

T'as juste à porter plainte (2021)
Keywords: Bibliographie; Nettoyer

Léa et Loïc (Parminou: Théâtre socialement engagé, 2024)
Keywords: Bibliographie; Nettoyer

"Droit au but" pour prévenir les violences subtiles (Parminou: Théâtre socialement engagé, 2021)
Keywords: Bibliographie; Nettoyer

Not in our house Chicago Theatre Community (Not in our house Chicago Theatre Community, 2017)
making safe spaces to do dangerous work
Keywords: Bibliographie; Nettoyer

Politique de prévention du harcèlement psychologique ou sexuel au travail et traitement des plaintes - Théâtre de la Ligue Nationale d'Improvisation (2020)
Keywords: Bibliographie; Nettoyer

*Charte canadienne des droits et libertés - Gouvernement du Canada
Les ressources en ligne des lois et reglements codifiés du Canada
Keywords: Bibliographie; Nettoyer

Rhetorical Constellations and the Inventional/Intersectional Possibilities of #MeToo - Bloomfield, Emma Frances (Journal of Communication Inquiry, 2019)
Keywords: Bibliographie; Nettoyer

En réponse à : « Check ton verre » - Scène & Sauve (Facebook, 2023)
Keywords: Bibliographie; Nettoyer

Le Centre psychologique pour artistes, un nouvel outil pour le milieu culturel - Renaud, Philippe (Le Devoir, 2024)
Keywords: Bibliographie; Nettoyer

Les artistes remettent en question la distribution de l’argent public en culture - Paré, Étienne (Le Devoir, 2024)
Keywords: Bibliographie; Nettoyer

Capsules sur le harcèlement au travail - Groupe d’aide et d’information sur le harcèlement sexuel au travail de la province de Québec (GAIHST, 2022)
Le Groupe d’aide et d’information sur le harcèlement au travail (GAIHST) lance 5 capsules vidéo dédiées aux travailleurs(euses) du Québec.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Accueil - Opération cocon (2024)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Avant Coup (Avant Coup)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Médiation citoyenne (Équijustice)
Équijustice offre des services de médiation citoyenne pour toute personne qui souhaite entamer une démarche de dialogue, en marge des procédures traditionnelles. Gratuit et confidentiel, le service est accessible à tous.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Nouvelle Accueil (Unison)
Unison a été formé en 2010 avec un objectif simple mais important en tête : pour s’assurer que les personnes qui composent l’industrie musicale canadienne ne soient jamais seules en période de crise. Créés par l’industrie, pour l’industrie, nous offrons des services financiers d’urgence et des conseils professionnels qui sauvent des vies et offrent un […]
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

shesaid.so Montreal: Project Crescendo (shesaid.so)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

900 000 $ pour contrer les agressions sexuelles et le harcèlement dans le milieu culturel québécois - Ministère de la Culture et des Communications (Gouvernement du Québec, 2018)
Keywords: Bibliographie; Nettoyer

Attouchements sexuels sur une élève : Romuald Pavy plaide coupable (Radio-Canada, 2011)
Le professeur de danse Romuald Pavy a plaidé coupable mardi matin à des accusations d'attouchements sexuels sur l'une de ses élèves.
Keywords: Bibliographie; Nettoyer

Le harcèlement en milieu de travail au Québec - Conseil des ressources humaines du secteur culturel (YouTube, 2019)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Harcèlement en milieu de travail dans les arts : à l’intention des travailleurs culturels - Conseil des ressources humaines du secteur culturel (YouTube, 2019)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Harcèlement en milieu de travail dans les arts : à l'intention des employeurs (YouTube, 2019)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Trousse à outil pour la gestion des ressources humaines : Harcèlement et violence dans le milieu de travail - Conseil des ressources humaines du secteur culturel. (2019)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

ANNULÉ(E): Réflexions sur la cancel culture - Lussier, Judith (Éditions Cardinal, 2021)
Après On peut plus rien dire, vendu à près de 7 000 exemplaires, Judith Lussier s’attaque à la culture de l’annulation avec son nouveau livre Annulé(e). Un brillant essai d’analyse qui, grâce à de nombreux exemples évocateurs et contemporains, fait le point sur un sujet brûlant d’actualité.« Alors que les réseaux sociaux ont permis à plus d’individus de prendre la parole et à différentes réalités d’être enfin nommées, il semble que le terrain discursif soit de plus en plus miné. Nous n’avons jamais pu autant nous exprimer librement, et pourtant, nous avons le sentiment que communiquer ses idées n’a jamais été aussi complexe et risqué. »C’est avec ce point de départ tout en nuances que la journaliste et essayiste Judith Lussier tente de comprendre la cancel culture. Cet essai examine ce phénomène complexe aux contours flous qui sème parfois la panique et alimente de nombreuses chroniques, sans faire l’économie d’une réflexion sur les dynamiques de pouvoir qui dictent sa trajectoire.
Keywords: Bibliographie; Nettoyer

Les professions de la culture et des communications au Québec en 2021 - Lubin, Marc-Ancy (Optique culture, 2024)
Keywords: Bibliographie; Nettoyer

LGBT People and the UK Cultural Sector: The Response of Libraries, Museums, Archives and Heritage since 1950 - Vincent, John (Routledge, 2016)
This book examines the complex and conflicting relationships between LGBT people and our cultural and heritage organisations including libraries, museums and
Keywords: Bibliographie; Nettoyer

Rehearsing Heterosexuality: "Unspoken" Truths in Dance Education - Risner, Doug (Dance Research Journal, 2002)
Keywords: Bibliographie; Nettoyer

Negotiating the gay male stereotype in ballet and modern dance - Polasek, Katherine M.; Roper, Emily A. (Research in Dance Education, 2011)
Dance, ballet and modern in particular, is culturally defined as a feminine activity in the United States. The purpose of the present study was to examine the experiences of professional male modern and ballet dancers in the United States. Semi-structured interviews were conducted with 12 current professional ballet and modern dancers. We examined the ways in which the dancers initially became involved in dance, any support or opposition they may have confronted, and the ways in which they negotiated the stereotypical assumptions surrounding men’s involvement in dance. Four emergent themes are discussed: (1) exposure to and entrance into dance; (2) the gay stereotype; (3) negotiating the gay stereotype; and (4) homophobia within the dance community. The social significance of this study is rooted in the ways in which our culture constructs gender, the body, and movement, restricting both males and females from using and exploring their bodies in ways not deemed gender-appropriate. Attention is also given to the ways in which we can create and nurture meaningful experiences for a greater number of individuals.
Keywords: Bibliographie; Nettoyer; gay men; homophobia; male dancers; masculinity

Dancing with Inclusivity: The Importance of Integrating Genderless Terminology into Swing Dance Spaces - Olander, Guinievere.R. (Unbound, 2022)
Keywords: Bibliographie; Nettoyer

Lesbian Lacunae: Invisible Spaces in Dance Education - Mozingo, Karen A. (Journal of Dance Education, 2005)
Recent research about sexuality and dance has begun to address the needs of gay male dancers, yet the needs of lesbian dancers have remained mostly absent from scholarly discourse. Exploring the lesbian lacunae, or invisible spaces of dance education, reveals the personal, political, and pedagogical implications of their existence within the dance community. The experiences of lesbian dancers “on the fringe” combined with new approaches to acknowledging lesbian artists and perspectives within dance history suggest the need for re-envisioning lesbian invisibility as a “liminal presence” within dance. In addition, ways dance educators can reduce the effects of heterocentrism within their institutions and celebrate the contributions of lesbian artists and educators to the field are proposed. By reconfiguring the invisibility of lesbian dancers as a liminal presence, we make visible the borders and limits of the dance profession's notions of sexuality and gender, acceptance and equality, and thereby strengthen our potential for dancing beyond them.
Keywords: Bibliographie; Nettoyer

“A Different Kind of Man”: Mediated Transgendered Subjectivity, Chaz Bono on Dancing With the Stars - Mocarski, Richard; Butler, Sim; Emmons, Betsy; Smallwood, Rachael (Journal of Communication Inquiry, 2013)
Chaz Bono’s appearance on Dancing with the Stars (DWTS) marks one of the first primetime, network appearances of a postoperative transgender person. This article deconstructs the mediated gender subjectivities of Bono as constructed by the show itself via prerecorded segments, costume and song choices, dance partner interaction, and judges’ commentaries as well as those projected by Bono during the live, unscripted portions of the show. Combining notions of the normalization of taboo sexual subjectivities through mediated contexts with lens of gender performativity, we demonstrate how transgender subjectivities are presented to a mainstream audience via such mediated choices, but also how Bono welds some agency to resist such normalization through his live performances. Bono’s appearance on DWTS stands as an important step toward acceptance of transgendered persons in mainstream society, however through a neutered, sex-free rhetoric as projected by the mediated portions of the show, his appearance is not without controversy. Additionally, we posit that Bono represents a transnormativity of a White, upper-class postoperative heterosexual male, which others all transgendered persons who fall outside of those hegemonic parallels of safe subjectivities.
Keywords: Bibliographie; Nettoyer

Publicizing transgender ballet dancers: a pas de deux of inclusion and reiterative gender norms - Mandradjieff, Mara; Alterowitz, Gretchen (Feminist Media Studies, 2023)
Over the last decade, mainstream media sources from the US and UK have shown an increased interest in topics involving transgender and non-binary populations. Yet, their portrayals of such individuals tend to reaffirm rather than challenge cisnormative ideas surrounding bodies and gender. In this article, we consider this ongoing trend within the highly body-centric, traditionally-gendered artform—classical ballet. With a transgender studies and dance studies lens, we analyze current discourse surrounding the recent move for classical ballet companies and schools to adapt casting and training curricula to better include non-binary dancers. Through these analyses we reveal ways media sensationalizes the transgender body by focusing on information regarding hormone therapy and surgeries, and with the topic of ballet in mind, how this transphobic move becomes intertwined with ballet-specific processes of reshaping the body. We claim that although these popular press pieces contribute to a greater awareness of the lived experiences of transgender and non-binary dancers, they simultaneously reiterate ongoing balletic gender tropes that mark the artform as feminine and designate particular body types and movements to specific binarized genders.
Keywords: Ballet; Bibliographie; Nettoyer; gender; media; non-binary; transgender

How is the Ballet World Including Non-Binary Dancers? - Lund, Rebekah (Dance Major Journal, 2022)
A few pioneers have shown the way, but who will follow?
Keywords: Bibliographie; Nettoyer

LGBTQ Welcoming Guidelines for Museums: developing a resource for the museum field - Leitch, Christopher; Youngs, Renae; Gavigan, Annette; Lesperance, Michael; Burns, William James; Cohen-Stratyner, Barbara; Hammond, Paul; Hansen, Jaden (Museums & Social Issues, 2016)
Beginning in 2014, the LGBTQ Alliance professional network of the American Alliance of Museums (AAM) met to develop and publish a broad set of LGBTQ Welcoming Guidelines for Museums. The authors sought to help museums be more inclusive of lesbian, gay, bisexual, transgender and queer staff and visitors. The Guidelines conform to the most recent established standards of professional practice in museums and touch on all areas of museum work; they may be viewed as part informational reference, part institutional self-assessment tool. The Guidelines were unveiled at the AAM’s 2016 annual meeting, and are now available at no charge online (http://www.aam-us.org/resources/professional-networks/lgbtq). The LGBTQ Alliance encourages readers to use and review the Guidelines and to make observations, critiques and corrections directly to the current chair, Mike Lesperance (mike@thedesignminds.com).
Keywords: Bibliographie; Coffre à outils; Lesbian; Nettoyer; bisexual; diversity; gay; inclusion; transgender

Rainbow dancing in Finland and the challenge of transgender inclusion - Kavoura, Anna; Rinne, Santtu (Routledge Handbook of Gender Politics in Sport and Physical Activity, 2022)
Traditionally, partner dances occur between a woman and a man, following rather conservative gender roles and rules. However, as a result of international lesbian, gay, bisexual, transgender, intersex, queer, asexual, allies and more (LGBTIQA+) activism, some social dancing events and competitions have made space for gender and sexual diversity. This chapter focuses on the Rainbow and Same-Sex dancing scene in Finland and its potential and challenges for transgender inclusion. We draw on data collected during the first author’s ethnographic and participatory action research study on trans-inclusive sport spaces and the second author’s experiences as a professional dance teacher and Rainbow trans dancer at both same-sex and mainstream dance competitions. Our findings reveal that the Rainbow dancing movement has helped make dancing more accessible and inclusive for members of the trans community through challenging traditional cis- and heteronormative dance roles and the men-lead/women-follow paradigm. Yet, certain challenges for trans-inclusion persist, such as the transphobic politics and rules of national and international dance associations. In concluding this chapter, we provide recommendations for enhancing access and positive experiences of trans people in dance, DanceSport and sport in general.
Keywords: Bibliographie; Nettoyer

Can Rainbow Become the New Pink? A study of ballet educators’ responses to the advancement of LGBTQ+ rights - Hawkes, Tracey (Researching Education Bulletin : Creative Arts Special Edition, 2023)
Keywords: Bibliographie; Nettoyer

Unsettling homocolonial frames of remembrance: Two-Spirit and Indigiqueer interventions at the museum - Failler, Angela (Memory Studies, 2023)
This article considers a Two-Spirit and Indigiqueer protest at the Canadian Museum for Human Rights as a flashpoint that exposes problems with how memory-making institutions are incorporating lesbian, gay, bisexual, trans and queer issues into their programming and/or collections. The protest brings into relief the museum’s investment in a homocolonial framing of remembrance for the way in which the telling of lesbian, gay, bisexual, trans and queer ‘progress’ is entangled with a settler colonial political economy wherein the tokenistic inclusion of some queers into the sexual citizenry happens alongside the dispossession, devaluing and criminalizing of others. I then undertake some preliminary ‘curatorial dreaming’ upon two other interventions–commentaries uploaded to a digital story bank by a Two-Spirit and an Indigenous queer museumgoer, and the short film Woman Dress by Plains Cree artist TJ Cuthand. Along with the protest, the commentaries and the film unsettle homocolonial frames of remembrance and provide critical openings towards decolonial queer memory work at the museum.
Keywords: Bibliographie; Nettoyer

More Than Two-Spirit: Queer Indigenous Sovereignty and Survivance in Museums - Cooper, Caitlin Skye (Université de Washington, 2017)
Keywords: Bibliographie; Nettoyer

What Makes a Lesbian Salsa Space Comfortable? Reconceptualising Safety and Homophobia - Boulila, Stefanie Claudine (Lesbian Geographies: Gender, place and power, 2015)
This chapter explores the sexual spatialisation of salsa dance spaces through the narratives of lesbian salsa dancers. It draws on conversations with seven
Keywords: Bibliographie; Nettoyer

A Gap in the Narrative: Exploring the Experiences of Trans Dancers Today - Best, Erica (Collège Ursinus, 2021)
Keywords: Bibliographie; Nettoyer

Hypermasculinity Makes the Queer Boy Faint - Alterio, Anthony M. (Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance, 2022)
Through the lens of personal experience, this chapter provides an exploration of the oft-concealed practices and hypermasculine ideals in dance education. Commercial, concert, and academic dance pedagogy continues to create and perpetuate homophobia that restricts the definition of “boy dancer” to the point of creating a false scarcity and competition to be the most cis-heteronormative male possible. Alterio argues this environment contributes to the perpetuation of discrimination against LGBTQIA+ dancers, the exclusion of non-cis boys, and lack of innovation in the field. Recommendations are offered to those interested in pushing the boundaries of performance and gender identity and a call for institutions to support this work.
Keywords: Bibliographie; Nettoyer

Briser le silence: Nathalie - Vastel, Michel (Éditions Libre Expression, 2005)
Keywords: Bibliographie; Nettoyer

Milieu littéraire : le harcèlement touche une écrivaine sur trois - UNEQ (union des écrivaines et des écrivains québécois, 2020)
L’Union des écrivaines et des écrivains québécois (UNEQ) révèle les résultats d’une enquête menée auprès des autrices et auteurs québécois début octobre. Ces chiffres démontrent sans équivoque le déséquilibre du rapport de force entre les partenaires du milieu, déséquilibre qui mène bien souvent à des comportements inacceptables et à une omerta intolérable.
Keywords: Bibliographie; Nettoyer

Violences sexuelles et abus de pouvoir dans le milieu littéraire : il est plus que temps d’agir - UNEQ (Union des écrivaines et des écrivains québécois, 2020)
L’UNEQ donne son appui à la lettre rédigée par un groupe constitué de plusieurs centaines de femmes et minorités de genre déterminées à faire cesser une situation qui ne peut plus durer dans le milieu littéraire.
Keywords: Bibliographie; Nettoyer

Le traitement médiatique du mouvement #AgressionNonDénoncée dans la presse écrite québécoise francophone - Savard-Moisan, Raphaëlle (Université du Québec à Montréal, 2017)
Keywords: Bibliographie; Nettoyer

Les pratiques des directrices l'industrie de la musique au Québec pour naviguer entre les exigences multiples de leurs fonctions - Saucier, Myriam (Université du Québec à Montréal, 2023)
Keywords: Bibliographie; Nettoyer

Rachat de Dare To Care par Cœur de pirate : un symbole pour les femmes en musique - Radio-Canada (Radio-Canada, 2021)
La rachat de la maison de disque par Béatrice Martin « a une symbolique très forte ».
Keywords: Bibliographie; Nettoyer

Véronique Cloutier condamne les gestes de son père - Radio-Canada (Radio-Canada, 2005)
Commentant pour la première fois les agressions sexuelles commises par Guy Cloutier, l'animatrice dit trouver « inacceptables » les gestes posés par son père à l'endroit de Nathalie Simard et de l'autre victime.
Keywords: Bibliographie; Nettoyer

La fondation de Nathalie Simard voit le jour - Radio-Canada (Radio-Canada, 2005)
« Il faut briser le silence », a déclaré Nathalie Simard lors du lancement de sa fondation qui viendra en aide aux organismes supportant les victimes de pédophilie.
Keywords: Bibliographie; Nettoyer

Guy Cloutier écope de trois ans et demi - Radio-Canada (Radio-Canada, 2004)
Le producteur et impresario Guy Cloutier a été condamné ce matin à 42 mois de prison par le juge Robert Sansfaçon. Cloutier avait avoué en novembre avoir agressé sexuellement deux enfants pendant de nombreuses années.
Keywords: Bibliographie; Nettoyer

Le mouvement #MoiAussi et ses événements marquants - Pineda, Améli (Le Devoir, 2022)
En octobre 2017 émergeait un mouvement de dénonciation planétaire.
Keywords: Bibliographie; Nettoyer

Julien Lacroix visé par des allégations d’agressions et d’inconduites sexuelles - Pineda, Améli (Le Devoir, 2020)
Neuf femmes racontent avoir été victimes d'agressions ou d'inconduites sexuelles de la part de l'humoriste et comédien.
Keywords: Bibliographie; Nettoyer

Michel Brûlé visé par une plainte d'agression sexuelle à Québec - Piedboeuf, Guillaume (La Tribune, 2017)
Une écrivaine de la Rive-Sud de Québec accuse l’éditeur Michel Brûlé de l’avoir agressée sexuellement à sa résidence du Vieux-Québec, en mars 2014, alors qu’elle venait lui proposer un manuscrit. Jill Côté a porté plainte à la police de Québec, vendredi, pour un incident dont M. Brûlé nie l’existence.
Keywords: Bibliographie; Nettoyer

L'écrivain jeunesse Maxime Roussy en prison pour 5 ans - Nguyen, Michael (Le Journal de Montréal, 2017)
Pendant cinq ans, de 2006 à 2011, Roussy avait profité d’une jeune lectrice pour assouvir ses fantasmes sadomasochistes.
Keywords: Bibliographie; Nettoyer

Les abus et la «loi du silence» dans la danse - Morneau, Caroline (Le Journal de Québec, 2019)
Abus psychologiques, physiques, sexuels: après les milieux du cinéma et de l’humour, on réalise que celui de la danse comporte son lot de scandales.
Keywords: Bibliographie; Nettoyer

Le patron des Éditions des Intouchables Michel Brûlé à son tour visé par des allégations d’inconduites sexuelles - Lévesque, Ève (Le Journal de Montréal, 2017)
Sept ex-employées se vident le cœur.
Keywords: Bibliographie; Nettoyer

Le #moiaussi de la danse - Lauzon, Véronique (2019)
Des acteurs du milieu de la danse brisent le silence sur les abus de pouvoir, le harcèlement psychologique et les agressions sexuelles vécus. Deux ans après #moiaussi, une quinzaine d’entre eux tentent de faire éclater l’omerta qui plombe cet environnement jugé toxique.
Keywords: Bibliographie; Nettoyer

Des musiciennes unies contre le sexisme - Lauzon, Véronique (La Presse, 2017)
Cent trente-cinq femmes issues du milieu musical ont décidé de dénoncer le sexisme et les injustices qu'elles subissent régulièrement au travail.
Keywords: Bibliographie; Nettoyer

Le milieu littéraire ébranlé par le mouvement de dénonciations - Lapointe, Josée (La Presse, 2020)
Le milieu littéraire fait face lui aussi au mouvement de dénonciations lancé il y a une dizaine de jours. Un groupe de 300 autrices et actrices de la chaîne du livre s’est formé de manière privée pour échanger à propos de cas d’inconduites sexuelles dont beaucoup ont été victimes.
Keywords: Bibliographie; Nettoyer

La littérature après #MoiAussi - Hébert-Dolbec, Anne-Frédérique (Le Devoir, 2022)
Le milieu littéraire attend encore des changements structurels importants, cinq ans après le début du mouvement.
Keywords: Bibliographie; Nettoyer

Vague de dénonciations : un an après: Qu’est-ce qui cloche dans le milieu culturel ? - Groguhé, Marissa (La Presse, 2021)
C’était il y a un an. En juillet 2020, une nouvelle vague de dénonciations d’agressions et d’inconduites sexuelles a déferlé sur les réseaux sociaux au Québec. Sans être la seule industrie touchée, le milieu culturel a été secoué par plusieurs scandales. Retour sur cet été de grands bouleversements.
Keywords: Bibliographie; Nettoyer

Between denunciations and precautions: the #Metoo movement in Quebec. A Critical Discourse Analysis of Quebec newspaper coverage in 2020 and 2017 - Glorieux, Charlotte (Université Charles, 2023)
Keywords: Bibliographie; Nettoyer

Une nouvelle accusation contre Eddy Toussaint: Son école de danse change de nom pour se dissocier du chorégraphe - Duhamel, Frédérik-Xavier (La Presse, 2022)
Alors que le chorégraphe Eddy Toussaint fait face à une deuxième accusation d’agression sexuelle, l’école et la troupe de ballet qu’il a fondées prennent leurs distances et changent de nom. Des spectacles ont aussi été retirés de l’affiche dans la foulée des accusations, mais la direction estime qu’il est injuste de pénaliser les danseurs.
Keywords: Bibliographie; Nettoyer

« Sous la ceinture, unies pour vaincre la culture du viol », un livre qui tombe à point - Radio-Canada (Radio-Canada, 2016)
Judith Lussier, l'une des auteurs du livre « Sous la ceinture, unis pour vaincre la culture du viol », souligne que ce phénomène est omniprésent et tend à banaliser les gestes des agresseurs.
Keywords: Bibliographie; Nettoyer

Ghomeshi, l’avant et l’après - Deglise, Fabien (Le Devoir, 2014)
L’ex-animateur-vedette emporte aussi dans sa chute la loi du silence envers les abus sexuels.
Keywords: Bibliographie; Nettoyer

Violences sexuelles et abus de pouvoir dans le milieu littéraire: il est plus que temps d’agir - Déclaration commune (Liberté – Art et politique, 2020)
Déclaration commune
Keywords: Bibliographie; Nettoyer

«Sous la ceinture»: La culture du viol, «pas une lubie de féministe» - Chabot, Kim (HuffPost, 2016)
«Sous la ceinture»: La culture du viol, «pas une lubie de féministe»
Keywords: Bibliographie; Nettoyer

Sexisme en danse : le mur du silence s’effrite au Québec - Carpentier, Mélanie (Jeu : revue de théâtre, 2018)
Un article de la revue Jeu, diffusée par la plateforme Érudit.
Keywords: Bibliographie; Nettoyer

Une nouvelle décrivant un viol entraîne la démission de la directrice de la revue «XYZ» - Caillou, Annabelle (Le Devoir, 2018)
Vanessa Courville a claqué la porte de la revue consacrée à la nouvelle littéraire.
Keywords: Bibliographie; Nettoyer

Comment parler des violences faites aux femmes en littérature? - Caillou, Annabelle (Le Devoir, 2018)
Trois spécialistes se penchent sur le sujet. Analyse.
Keywords: Bibliographie; Nettoyer

Léa Clermont-Dion accuse Michel Venne de l’avoir agressée - Bussières, Ian; Piedboeuf, Guillaume (Le Soleil, 2017)
L’écrivaine et militante Léa Clermont-Dion, qui avait révélé en 2014 avoir été agressée sexuellement à l’âge de 17 ans, a déposé une plainte à la police contre le fondateur de l’Institut du Nouveau Monde, Michel Venne. Des allégations d’agression sexuelle que nie ce dernier.
Keywords: Bibliographie; Nettoyer

Vague de dénonciations: des têtes tombent dans le milieu artistique - Bélanger, Cédric (Le Journal de Québec, 2020)
Les dénonciations font tomber Maripier Morin, Bernard Adamus et le patron de Dare To Care.
Keywords: Bibliographie; Nettoyer

Michel Venne coupable d’agression sexuelle - Béland, Gabriel (La Presse, 2021)
L’ancien journaliste Michel Venne a été reconnu coupable mercredi d’agression et exploitation sexuelle sur Léa Clermont-Dion alors qu’elle avait 17 ans. La poursuite espère que ce verdict encouragera d’autres victimes à porter plainte.
Keywords: Bibliographie; Nettoyer

Michel Brûlé reconnu coupable d’agression sexuelle - Béland, Gabriel (La Presse, 2020)
L’éditeur Michel Brûlé a été reconnu coupable mercredi d’agression sexuelle à l’endroit d’une auteure venue le rencontrer pour présenter un manuscrit.
Keywords: Bibliographie; Nettoyer

Best Practices for scenes involving nudity, intimacy, simulated sex and sexual violence - ACTRA (2020)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Personal Safety for Dance (2022)
Personal Safety for Dance exists to develop a dance environment that is free from abuse, open, and supportive for all in dance.
Keywords: Bibliographie; Nettoyer

Je n'en ai jamais parlé à personne - Delvaux, Martine (Éditions Heliotrope, 2020)
«En octobre 2017, devant la vague de témoignages suscitée par le mouvement #moiaussi, j’ai senti une urgence : une fois sorties du silence, nous ne devions pas y retourner. C’est la raison pour laquelle j’ai lancé un appel. Ce livre est une chambre d’échos. Un chœur. Sans déesse ni héroïne en tête, des voix avancent. Nous faisons front commun.» Martine Delvaux «Je n'en ai jamais parlé à personne» : paroles recueillies et agencées par Martine Delvaux
Keywords: Bibliographie; Nettoyer

Un hommage pour Romane Bonnier (2021)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Harcèlement et inconduites dans le milieu artistique. Quel est mon rôle ? - ADISQ; RIDEAU (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Entente collective 2022-2024 entre l'Orchestre Métropolitain et la Guilde des musiciens et musiciennes du Québec (2022)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Entente collective 2023-2026 entre la Guilde des musiciens et musiciennes du Québec et l'Orchestre l'Agora (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Entente collective 2023 - 2027 entre la Guilde des musiciens et musiciennes du Québec et l’Orchestre symphonique du Saguenay-Lac-Saint-Jean (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Violences conjugales et sexuelles: Formations gratuites (Juripop, 2024)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Collections - Groupe de recherche et d'intervention psychosociale (GRIP) (GRIP, 2024)
Le GRIP intervient en milieu festif (rave, festival) afin de réduire les méfaits associés à la consommation de drogues et de prévenir ses usages problématiques.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Harcèlement au travail - Commission des normes de l'équité de la santé et de la sécurité du travail (CNESST) (2021)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Accueil - CRIPCAS (2024)
Centre de recherche interdisciplinaire sur les problèmes conjugaux et les agressions sexuelles
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Les premier·ères coordonnateurs et coordonnatrices d’intimité certifié·es du Québec - Coordination d'intimité Québec (ICCQ, 2023)
Les coordonnateurs et coordonnatrices d'intimité pour le cinéma et la télévision. Formé·e·s par les programmes de certification qui ont établi le standard du rôle à l'international et ailleurs au Canada, Mo Matton, Stephanie Breton et Mimi Côté représentent la branche du Québec d'Intimacy Coordinato
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Diversity, Equity, Inclusion & Belonging Committee (ACTRA National, 2023)
ACTRA National’s Diversity, Equity, Inclusion & Belonging Committee promotes the principles concerning the casting of People of Colour, Indigenous Peoples and people with disabilities. The best initiatives are driven by members. We can better shape initiatives to support you by getting to know our membership and understanding your experiences. We welcome your input and your […]
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Mesures de soutien et d’inclusion des personnes trans et des personnes non binaires en milieu de travail : Guide pour les employeurs et les syndicats - Table nationale de lutte contre l'homophobie et la transphobie des réseaux de l'éducation (2019)
Keywords: Bibliographie; Nettoyer

Victim Services - ReadtheCode (2019)
Keywords: Nettoyer; À ajouter

Soutien psychologique (Guilde des musiciens et musiciennes du Québec, 2022)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Service des relations de travail | 514 842-2866, poste 241 - GMMQ - Guilde des musiciens et musiciennes du Québec
Keywords: Nettoyer; À ajouter

GRIP-Prévention - Groupe de recherche et d'intervention psychosociale (GRIP, 2024)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Formations et autres ressources - Conseil des ressources humaines du secteur culturel (Milieux de travail respectueux dans les arts, 2021)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Modèle de politique pour la création d'un milieu de travail sain, respectueux et exempt de discrimination, de harcèlement et de violence - Labine, Lise; Lorquet, Me Sébastien (L’Association des théâtres francophones du Canada, 2018)
L’Association des théâtres francophones du Canada a développé ce modèle de politique pour ses compagnies membres avec l’appui de Théâtre Action.
Keywords: Bibliographie; Nettoyer

Formation sur le respect en milieu du travail - Conseil des Arts du Canada (2019)
Cette session d’information au sujet de milieux de travail respectueux explore les raisons derrière l’augmentation du nombre de problèmes de comportement en milieu de travail, de son impact, ainsi que de l'importance de définir les attentes en matière de comportement afin d'aider les employeurs et les organismes à gérer, contrôler et prévenir les comportements pouvant constituer du harcèlement (harcèlement sexuel, discrimination, intimidation et violence ).
Keywords: Bibliographie; Nettoyer

Our Music My Body: 2017 Campaign & Survey Report - OurMusicMyBody (2017)
Keywords: Bibliographie; Nettoyer

Kesha’s Comeback and the Stakes of Live Performance: Connecting through Trauma at the 2018 Grammy Awards - Hearfield, Katelyn (Journal of Musicological Research, 2021)
The use of live popular music performance as a platform to address gendered and sexual violence and trauma within the popular music industry can be demonstrated through the analysis of Kesha’s performance of “Praying” at the 2018 Grammy Awards. Analyzing the artist’s vocal and artistic delivery, in addition to her public persona following her allegations of sexual abuse against producer Lukasz Gottwald (Dr. Luke), illustrates how live performance—building on and contrasting with social media campaigns, such as #FreeKesha and #MeToo, and studio recordings—is a uniquely effective mode of processing individual and collective trauma.
Keywords: Bibliographie; Nettoyer

Capsule sur le GRIP, projet Spotlight (YouTube, 2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

L'Aparté - Formation ADISQ (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Capsule Collectif Social - Formation ADISQ (YouTube, 2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Ressources harcèlement (Guilde des musiciens et musiciennes du Québec)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Pour une culture du consentement - Les frères Seaborn (2022)
Keywords: Bibliographie; Nettoyer

#MeToo et la justice réparatrice (Curio.ca, 2022)
Ça fait plus de 5 ans que le mouvement #MeToo (#MoiAussi) a commencé. Depuis, de nombreuses victimes de crimes sexuels critiquent notre système de justice traditionnel. Mais il existe une autre solution, fondée sur des principes et des processus autochtones : la justice réparatrice. Comment fonctionne-t-elle exactement? Tom-Éliot Girard est …
Keywords: Coffre à outils; Nettoyer; À ajouter

Porter plainte: récit - Clermont-Dion, Léa (Le Cheval d'août, 2023)
"Agressée sexuellement par son patron à l'âge de dix-sept ans, Léa Clermont-Dion décide, près d'une décennie plus tard, de poursuivre l'agresseur en justice. Elle consignera son expérience dans son journal jusqu'au procès. Pendant ce temps, l'affaire Harvey Weinstein déclenche le mouvement #MeToo, et des millions de femmes dénoncent la culture du viol à visage découvert. La déposition criante de vérité de Porter plainte témoigne de la froide autorité du droit et des luttes des victimes de crimes sexuels, qui reprennent la parole qu'on leur a soustraite"--Back cover
Keywords: Bibliographie; Nettoyer

Le privilège de dénoncer: justice pour toutes les victimes de violences sexuelles - Souffrant, Kharoll-Ann (Éditions du remue-ménage, 2022)
Keywords: Bibliographie; Nettoyer

Faire justice: moralisme progressiste et pratiques punitives dans la lutte contre les violences sexistes - Deck Marsault, Elsa (La Fabrique éditions, 2023)
Keywords: Bibliographie; Nettoyer; Restorative justice; Sexual minorities; Violence against; Women

Le programme Possibilités de justice réparatrice (médiation entre la victime et le délinquant) - Service correctionnel Canada (2020)
Le programme Possibilités de justice réparatrice (médiation entre la victime et le délinquant)
Keywords: Bibliographie; Nettoyer

Réseau d'aide aux hommes pour une société sans violence (À coeur d'homme, 2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Agir ensemble contre les agressions à caractère sexuel (Programme Empreinte)
« Empreinte – Agir ensemble contre les agressions à caractère sexuel est un nouveau programme de prévention des agressions à caractère sexuel destiné aux jeunes de niveau secondaire, à leurs parents et au personnel scolaire. Ce programme a été développé conjointement par les professeures Manon Bergeron et Martine Hébert, du département de sexologie de l’UQAM ainsi que par le Regroupement québécois des centres d’aide et de lutte contre les agressions à caractère sexuel (RQCALACS). Ce projet se réalise avec le Service aux collectivités de l'UQAM.»
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Intégrer les personnes trans en milieu de travail - Fondation émergence; Aide aux Trans du Québec (ATQ) (2018)
Keywords: Bibliographie; Nettoyer

Modèle de politique en matière de harcèlement psychologique ou sexuel au travail et de traitement des plaintes - Commission des normes de l'équité de la santé et de la sécurité du travail (CNESST) (2024)
Notre modèle de politique est présentement en cours de révision pour tenir compte des nouvelles dispositions prévues par la Loi visant à prévenir et à combattre le harcèlement psychologique et la violence à caractère sexuel en milieu de travail
Keywords: Bibliographie; Nettoyer

Webinaire contre le harcèlement et les violences (milieu cirque) pour artistes & travailleuses/eurs (2020)
En partenariat avec Juripop, En Piste vous présente le webinaire qui fût présenté dans le cadre de sa clinique contre le harcèlement et les violences dans le milieu cirque, qui a eu lieu le mardi 25 août 2020. Ce webinaire présente les services du Centre d'aide aux victimes d'actes criminels (CAVAC) et du Groupe d'aide et d'information sur le harcèlement sexuel au travail (GAIHST). Pour plus d'information et de ressources, visitez notre site web : www.enpiste.qc.ca
Keywords: Bibliographie; Nettoyer; À ajouter

Pour des milieux de travail exempts de harcèlement - Ordre des conseillers en ressources humaines et en relations industrielles agréés du Québec. (Carrefour RH, 2024)
Guide pour améliorer ses pratiques de prévention, d'intervention et de soutien dans des situations de harcèlement au travail.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Rebâtir (2023)
Consultation juridique sans frais pour les personnes victimes de violence sexuelle et de violence conjugale.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Commande un Angelot (2021)
« Le protocole d’accréditation Commande un Angelot a été conçu afin de s’attaquer aux violences à caractère sexuel dans les bars et les événements festifs ou sociaux. Celui-ci vise à prévenir ces situations et à venir en aide aux personnes en difficulté. Le Collectif social, un organisme sans but lucratif qui souhaite déployer et soutenir la réalisation d’initiatives de nature communautaire ou sociale qui répondent aux besoins des communautés étudiantes des établissements d’enseignement supérieur, est derrière ce projet. »
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Code d'éthique - Association québécoise de l'indusstrie du disque, du spectacle et de la vidéo (ADISQ) (2023)
Keywords: Bibliographie; Nettoyer

Déclaration pour un environnement de travail exempt de harcèlement dans le milieu culturel québécois (Regroupement des arts interdisciplinaires du Québec, 2024)
ATTENDU QUE des associations d’artistes et des associations de producteurs (ci-après collectivement les « Associations ») ainsi que les regroupements du milieu culturel (ci-après collectivement les « Regroupements »), conviennent que toutes les personnes œuvrant dans le milieu culturel québécois, quel que ce soit leur rôle ou leurs responsabilités, devraient être en mesure d’exercer [...]
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Dénoncez un incident sur le plateau (ACTRA Montreal, 2024)
Grâce aux rapports anonymes, nous sommes informés des problèmes au fur et à mesure qu’ils surviennent. Il est possible de rester anonyme, mais il est préférable de laisser vos coordonnées pour que nous puissions vous contacter. Nous ne donnerons jamais suite à une réclamation sans votre consentement!
Keywords: Bibliographie; Nettoyer

Coordonnateur·rice·s de l'intimité - ACTRA Montréal (ACTRA Montreal, 2024)
Les coordonnateurs d'intimité sont des spécialistes de la production qui planifient, supervisent et coordonnent les scènes intimes filmées.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Code de Conduite pour les arts de la scène au Canada - Milieux de travail respectueux dans les arts (2019)
Keywords: Bibliographie; Dans le rapport; Nettoyer

Faire face au harcèlement en milieu de travail culturel: Un rapport sur les mécanismes de dénonciation et d’enquête existants et potentiels pour travailleurs et employeurs culturels - Labine, Lise; LeSage, Jeanne; Gagnon, Grégoire (Conseil des ressources humaines du secteur culturel, 2020)
Keywords: Bibliographie; Coffre à outils; Nettoyer

Code de conduite - Industries créatrices du Canada (lirelecode.ca, 2018)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Tous les spectacles (Parminou: Théâtre socialement engagé, 2024)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Debranchée (Unplugged) - Laurier, Mathilde; St-Laurent, Marie-Claude; Hébert, Maude; Milot, Marie-Ève (2017)
Débranchée (Unplugged) est une fiction qui traite des violences sexuelles dans le monde adolescent. La pièce raconte l'histoire de deux amies ébranlées par les rumeurs d'agressions sexuelles qui se propagent à haute vitesse dans leur école. Quand Allison brise la loi du silence, toute une chaîne de réactions s'enclenche. Des témoignages fusent, donnant une voix à toutes ces violences sexuelles trop souvent vécues dans l'anonymat. Devant l'ampleur du phénomène, les deux protagonistes cherchent à transformer l'explosion créée en un élan de solidarité. Elles iront jusqu'au bout. Le show aura lieu.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Campagne de sensibilisation : Harcèlement au travail - Groupe d’aide et d’information sur le harcèlement sexuel au travail de la province de Québec (GAIHST, 2023)
GAIHST Inc est un organisme communautaire de la province de Québec qui vient en aide aux travailleurs et travailleuses ayant subi du harcèlement au travail.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

SOS violence conjugale (SOS violence conjugale)
Au service de l’ensemble de la population du Québec, SOS violence conjugale offre des services d’accueil, d’information, de sensibilisation, de soutien et de référence bilingues, gratuits, anonymes et confidentiels 24h sur 24.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

En mouvement vers une culture du consentement (RQCALACS, 2024)
Les CALACS offrent des services de soutien aux victimes d’agressions à caractère sexuel. Trouvez de l’aide, partout à travers le Québec.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Contribuer à une culture exempte de harcèlement (SST) - AQTIS 514 IATSE (L'Alliance québécoise des techniciens et techniciennes de l'image et du son, section locale 514, 2024)
« Parce que la sécurité au travail est une responsabilité collective, luttons ensemble pour éliminer le harcèlement ! Votre syndicat a fait de cet enjeu sa priorité. Notre industrie, atypique et fortement compétitive, peut engendrer de nombreux abus et freiner la dénonciation. La précarité d'emploi, la hiérarchisation des fonctions, le taux de rendement exigé, le niveau de stress et la crainte de représailles en sont les principaux facteurs. L'AQTIS 514 IATSE met à votre disposition une formation gratuite et interactive pour vous aider à travailler dans un environnement sécuritaire. OBJECTIFS : Reconnaître les situations qui s’apparentent à du harcèlement psychologique ou sexuel au travail; Savoir adopter une posture d’affirmation face à des conduites d’incivilité, d’intimidation ou de harcèlement en vue de les faire cesser; Connaître les mécanismes pour signaler ou dénoncer les conduites s’apparentant à de l’intimidation ou du harcèlement.»
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Centre d'aide aux victimes d'actes criminels (CAVAC, 2024)
«Le Réseau des CAVAC est présent dans toutes les régions du Québec. Plus de 185 portes qui vous donnent accès à des professionnel(le)s formé(e)s en intervention ».
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Prévenir et gérer le harcèlement - Formations AQPM (Formations : Des classes de perfectionnement pour les professionnel-(le)s de l'industrie audiovisuel, 2023)
« Cette formation permettra aux producteurs et à leurs représentants de reconnaître les situations de harcèlement ou celles qui sont à risque de le devenir afin de comprendre les rôles et responsabilités qui leur reviennent. Les particularités propres à notre industrie y seront également abordées. Formateur: Me Frédéric Massé Borden, Ladner, Gervais »
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Collectif social collective - Le Collectif social (Lutte contre les violences sexuelles, 2023)
Offrent des formations sur mesure, ainsi que les formations : - Prévenir la violence sexuelle dans les événements festifs ou sociaux - Les violences sexuelles chez les communautés LGBTQIA2S+ - Devenir un témoin actif
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Code d'éthique - Association nationale des éditeurs de livres (ANEL) (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

harcelement@uda.ca - Union des artistes
Pour toute question sur le harcèlement psychologique (y compris le harcèlement sexuel) ou encore sur la santé et la sécurité au travail à l’UDA, écrivez à l’adresse harcelement@uda.ca ou communiquez avec les conseillères et conseillers en relations du travail suivants : Karine Hervieux-Michaud 514-288-7150, poste 1339 , Émilie Lachance 514-288-7150, poste 1252 Catherine Leszkiewicz 514-288-7150, poste 1264 Bruno Massicotte-Picard 514-288-7150, poste 1338 Rémi Garon 514-288-7150, poste 1235 Marie Fisette 514-288-7150, poste 1254
Keywords: Bibliographie; Nettoyer

Code de conduite [Affiche] (2024)
18 x 24 harcèlement affiche WEB
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Inconduite sexuelle: deux acteurs largués - Gendron-Martin, Raphaël (Le Journal de Montréal, 2020)
La valse des dénonciations pour inconduite sexuelle touchant le milieu culturel se poursuit.
Keywords: Bibliographie; Nettoyer

Safia Nolin accuse, Maripier Morin s’excuse - Groguhé, Marissa (La Presse, 2020)
L’auteure-compositrice-interprète Safia Nolin a provoqué une onde de choc en accusant mardi Maripier Morin de s’être livrée à du harcèlement sexuel, d’avoir commis une agression physique et d’avoir proféré des propos racistes lors d’une soirée dans un bar il y a deux ans. Des allégations en partie admises par l’animatrice télé, qui a présenté ses excuses le lendemain.
Keywords: Bibliographie; Nettoyer

Le milieu du jeu vidéo est-il indécrottablement discriminatoire? - Baillargeon, Stéphane (Le Devoir, 2020)
Le mouvement #MoiAussi frappe l’industrie de la manette et son sexisme systémique.
Keywords: Bibliographie; Nettoyer

La Cour d’appel donne raison à Gilbert Rozon - Corriveau, Jeanne (Le Devoir, 2020)
Le tribunal a annulé l’autorisation de l’action collective des Courageuses contre l’ancien magnat de l’humour.
Keywords: Bibliographie; Nettoyer

Allégations de nature sexuelle: Gilbert Rozon visé par neuf femmes - Pineda, Améli (Le Devoir, 2017)
Neuf femmes racontent au «Devoir» ainsi qu’au 98,5 FM avoir été victimes de harcèlement et d’agressions sexuelles de la part du fondateur de Juste pour rire, Gilbert Rozon, et ce, dans la foulée du mouvement #MeToo. Certaines d'entre elles étaient même mineures au moment des incidents rapportés. Et pendant des années, elles ont cru être seules.
Keywords: Bibliographie; Nettoyer

Inconduites sexuelles reprochées à Éric Salvail - Gagnon, Katia; Vallet, Stéphanie (La Presse, 2017)
Avances sexuelles en string, parties intimes exhibées ou empoignées, tentatives de séduction insistantes dans des salles de montage: 11 personnes ont raconté à La Presse avoir subi des inconduites, ou en avoir été témoins, de la part du producteur et animateur Éric Salvail, la plupart du temps dans un contexte professionnel.
Keywords: Bibliographie; Nettoyer

From victim to survivor - and from survivor to victim: Reconceptualising the survivor journey - Jordan, Jan (Sexual Abuse in Australia and New Zealand, 2013)
Being recognized as a rape survivor has often been interpreted as implying a linear progression from the negative state of victimisation, experienced in the presence of the offender, to a stronger, more positive state, typically facilitated by external support mechanisms. Drawing primarily on interviews conducted with women victimised by New Zealand serial rapist, Malcolm Rewa, this article challenges the concept of a journey 'from victim to survivor' by considering the multiple ways in which these women sought to protect themselves and survive during the attack while also experiencing aspects of their postattack involvement with individuals and agencies as further victimisation. The article concludes by outlining some initial implications regarding what this may mean for professionals working with victim/survivors of sexual violence.
Keywords: Bibliographie; Nettoyer

Beyond Victim or Survivor: Sexual Violence, Identity and Feminist Theory and Practice - Kelly, Liz; Burton, Sheila; Regan, Linda (Sexualizing the Social, 1996)
Keywords: Bibliographie; Nettoyer

Rethinking sexual violence labels: exploring the impact of ‘victim’ and ‘survivor’ discourse - O’Shea, Brittany; Feicht, Rebecca; Brown, Marion; Numer, Matthew (European Journal of Psychotraumatology, 2024)
Background: Universities’ responses to sexual violence have faced scrutiny for their lack of proactiveness and their failure to address campus socio-cultural norms that contribute to rape myth acceptance. The labels victim and survivor play a crucial role in shaping attitudes toward sexual violence, but there is limited research on how university students perceive these labels. Objective: This paper explores sexual violence labels and their role in perpetuating rape culture. Undergraduate university students’ beliefs on using the label survivor instead of victim to describe someone who has experienced sexual violence were examined to consider how these labels create societal discourse on sexual violence. Method: The study draws on qualitative data collected from undergraduate students in Canada and the United States through open-response questions in an interactive textbook. Data were analysed and interpreted using a multi-method approach that combined principles of Critical Discourse Analysis and Feminist Poststructuralism. Direct quotes and word clouds from participants’ responses are used as evidence and to visually display discourse. Results: Findings revealed that participants recognised the negative societal discourses associated with the label victim and supported using survivor to challenge perceptions of sexual violence. Despite this, participants expressed hesitancy to adopt the label survivor because of the potential negative implications, such as the label promoting the allocation of individual blame, increasing barriers to justice, and reducing the perceived severity of sexual violence. Conclusions: This study underscores the complexities of sexual violence labels, the influence of language in shaping societal perceptions, and the need for a more comprehensive and equitable approach to responding to sexual violence. Dichotomy of Labels and Nuanced Perceptions: Sexual violence labels shape identity perceptions. Participants dichotomised the labels victim and survivor, associating one with negative attributes and the other with positive attributes. However, nuanced views of how people perceive and identify with these labels challenge distinct categories. Victims being negatively perceived, while survivors are admired for their resiliency highlights complexities in societal expectations that may not fully address the underlying determinants of sexual violence.Role of Language in Reproduction of Rape Culture: Poststructuralist theories emphasise the role of language in the production and maintenance of discourse. The study shows that victim discourse is steeped in rape myths. The historical discourse surrounding the label may contribute to the perpetuation of negative attitudes and behaviours toward victims of sexual violence. The emergence of the label survivor reflects a societal shift, but findings suggest this may lead to societal complacency towards sexual violence.Spectrum of Severity and Societal Empathy: Participants’ understanding of sexual violence as a spectrum of severity may lead to unequal levels of empathy and support. This discourse creates positions of dominance and oppression, potentially marginalising certain groups who are disproportionately affected by sexual violence. The study highlights how severity discourse can influence institutional agendas and may result in political and institutional neglect of sexual violence. Dichotomy of Labels and Nuanced Perceptions: Sexual violence labels shape identity perceptions. Participants dichotomised the labels victim and survivor, associating one with negative attributes and the other with positive attributes. However, nuanced views of how people perceive and identify with these labels challenge distinct categories. Victims being negatively perceived, while survivors are admired for their resiliency highlights complexities in societal expectations that may not fully address the underlying determinants of sexual violence. Role of Language in Reproduction of Rape Culture: Poststructuralist theories emphasise the role of language in the production and maintenance of discourse. The study shows that victim discourse is steeped in rape myths. The historical discourse surrounding the label may contribute to the perpetuation of negative attitudes and behaviours toward victims of sexual violence. The emergence of the label survivor reflects a societal shift, but findings suggest this may lead to societal complacency towards sexual violence. Spectrum of Severity and Societal Empathy: Participants’ understanding of sexual violence as a spectrum of severity may lead to unequal levels of empathy and support. This discourse creates positions of dominance and oppression, potentially marginalising certain groups who are disproportionately affected by sexual violence. The study highlights how severity discourse can influence institutional agendas and may result in political and institutional neglect of sexual violence.
Keywords: Bibliographie; Nettoyer

The Story of Jane Doe: A Book About Rape - Doe, Jane (Vintage Canada, 2004)
Keywords: Bibliographie; Nettoyer

Le respect de la dignité des femmes dévoilant une agression à caractère sexuel:perspectives d'intervenantes sociales et communautaires Montréalaises - Souffrant, Kharoll-Ann (Université McGill, 2019)
Keywords: Bibliographie; Nettoyer

Gros été pour la culture du viol - Elkouri, Rima (La Presse, 2022)
Nouveau scandale de viol collectif à Hockey Canada. Allégations d’inconduites sexuelles contre l’humoriste Philippe Bond. Absolution conditionnelle pour l’ingénieur Simon Houle coupable d’agression sexuelle…
Keywords: Bibliographie; Nettoyer

Quand se taire n’est plus une option - Papineau, Philippe; Renaud, Philippe (Le Devoir, 2020)
Keywords: Bibliographie; Nettoyer

Ubisoft : les démissions ne viendront pas à bout de la toxicité, disent des employés - Prévost, Hugo (Radio-Canada, 2020)
Le géant du jeu vidéo est plongé dans la tourmente depuis des semaines en raison d'allégations de harcèlement.
Keywords: Bibliographie; Nettoyer

Un enseignant de l'École nationale de cirque accusé de crimes sexuels - Radio-Canada (Radio-Canada, 2018)
L'entraîneur Marcelo Berti Marques fait face à quatre chefs d'accusation, entre autres pour avoir envoyé une photo de ses organes génitaux à un de ses anciens élèves de l'École nationale de cirque, à Montréal. Sa présumée victime est soulagée, mais craint qu'il ait fait d'autres victimes.
Keywords: Bibliographie; Nettoyer

Vague de dénonciations : au tour du cirque de faire son examen de conscience - Siag, Jean (La Presse, 2020)
Depuis quelques semaines déjà, les témoignages de violences sexuelles dans le monde du cirque se multiplient sur les réseaux sociaux. Au point où le regroupement national des arts du cirque, En Piste, a décidé de lancer dès mardi avec Juripop une clinique « contre le harcèlement et les violences dans le milieu du cirque ». La Presse a parlé aux instigateurs de Victims_Voices_Circus, espace virtuel où la parole de nombreuses artistes s’est fait entendre.
Keywords: Bibliographie; Nettoyer

Harcèlement à Ubisoft : la joueuse professionnelle Stéphanie Harvey témoigne - Agence France-Presse (Radio-Canada, 2020)
Une vague de dénonciations secoue Ubisoft et l'industrie du jeu vidéo depuis quelques semaines.
Keywords: Bibliographie; Nettoyer

Pollitique contre le harcèlement et l’intimidation et la promotion d’un environnement sain - École nationale de théâtre du Canada (Département du bureau de la direction générale, 2023)
Keywords: Bibliographie; Nettoyer

*Loi visant à prévenir et à combattre les violences à caractère sexuel dans les établissements d’enseignement supérieur - Gouvernement du Québec (RLRQ c P-22.1, 2017)
Keywords: Bibliographie; Nettoyer

Cadre de référence évolutif des objectifs et contenus de prévention des violences à caractère sexuel en milieu d’enseignement supérieur - Fradette-Drouin, Laurie; Bergeron, Manon (Chaire de recherche sur les violences sexistes et sexuelles en milieu d’enseignement supérieur. Université du Québec à montréal, 2022)
Keywords: Bibliographie; Nettoyer

Violence sexuelle - Bureau de la médiation et du signalement (Université McGill, 2024)
Tous les membres de McGill ont droit au soutien sans équivoque du Bureau d’intervention, de prévention et d’éducation en matière de violence sexuelle (OSVRSE – Office for Sexual Violence Response, Support, and Education), que ces membres déposent ou non un signalement officiel. L’OSVRSE peut vous fournir des services de soutien, vous aider à obtenir des accommodements scolaires ou professionnels et vous expliquer les différents processus de signalement — que vous envisagiez de faire un signalement dans le cadre de la Politique contre la violence sexuelle de McGill ou à l’extérieur — afin que vous puissiez décider ce qui vous convient le mieux. Il n’est pas nécessaire de déposer un signalement officiel pour accéder à du soutien, demander des accommodements possibles ou obtenir de l’information auprès de l’OSVRSE. Vous pouvez prendre rendez-vous directement avec l’OSVRSE ici. Si vous souhaitez déposer un signalement en vertu de la Politique contre la violence sexuelle de McGill ou en apprendre davantage au sujet des processus offerts (médiation/enquête), veuillez communiquer avec le Bureau de la médiation et du signalement (OMR). Visitez notre page Demander une consultation pour en savoir plus. Tous les membres de la communauté universitaire ont le droit de travailler et d’apprendre dans un environnement exempt de violence sexuelle. L’Université reconnaît que, même si la violence sexuelle touche tous les membres de la société, ce type de maltraitance et ses conséquences peuvent atteindre de manière disproportionnée des membres de groupes sociaux aux prises avec des formes intersectionnelles de discrimination systémique ou d’obstacles (fondés notamment sur l’identité et l’expression sexuelles, l’orientation sexuelle, la race, la religion, l’appartenance à un groupe autochtone, l’ethnicité, l’invalidité ou la classe sociale).  Qu’est-ce que la violence sexuelle ? La violence sexuelle est un terme générique qui désigne un continuum d’actes de nature sexuelle qui sont menacés, tentés ou commis à l’encontre d’une personne sans son consentement. Elle peut être dirigée vers l’orientation sexuelle, l’expression sexuelle ou de genre ou l’identité de genre d’une personne. Cela inclut l’agression sexuelle, le harcèlement sexuel, le harcèlement criminel, la cyberviolence, la distribution non consensuelle d’images sexuelles, le voyeurisme, etc. L’OSVRSE de McGill présente de plus amples renseignements sur la violence sexuelle sur son site Web. Définition dans la politique La définition officielle de la violence sexuelle adoptée à McGill se trouve à l’alinéa 7k) de la Politique contre la violence sexuelle de McGill : « Violence sexuelle » s’entend d’un ou de plusieurs actes sexuels, commis ou tentés, qui ciblent la sexualité, l’identité ou l’expression sexuelle d’une personne, ou toute menace de commettre de tels actes contre une personne sans son consentement. La violence sexuelle peut se manifester en personne, au téléphone ou en ligne. Elle englobe : i) l’agression sexuelle qui désigne un contact sexuel avec une autre personne sans son consentement; ii) le harcèlement sexuel, qui désigne une conduite de nature sexuelle A) selon laquelle l’activité sexuelle : est établie comme modalité ou condition explicite ou implicite d’emploi d’une personne ou de statut dans un cours, un programme ou une activité; ou  est utilisée comme motif sous-tendant une décision en matière d’emploi ou d’éducation qui a des incidences sur une personne; OU, B) qui a pour effet de nuire au travail ou au rendement universitaire d’une personne quand il est reconnu, ou devrait être reconnu, que cette conduite est importune;  iii) « traquer » qui désigne la surveillance ou le fait de suivre indûment une autre personne alors que cette personne, déposant une divulgation ou un signalement, a l’impression que cette traque a un lien avec le sexe ou l’identité sexuelle; iv) « exhibitionnisme » qui désigne l’exposition de ses organes sexuels à une autre personne dans un lieu public ou de manière menaçante ou choquante pour cette personne; v) « voyeurisme » qui désigne l’observation furtive ou l’enregistrement d’une personne au moyen d’un dispositif mécanique ou électronique; vi) « diffusion d’images sexuelles » qui désigne la distribution d’une image, photo ou vidéo de nature sexuelle d’une personne sans son consentement; et vii) « exploitation sexuelle » qui désigne l’abus ou l’exploitation de la sexualité d’une autre personne aux fins d’une gratification sexuelle, d’un gain pécuniaire, d’un avantage personnel ou à tout autre fin non légitime.
Keywords: Bibliographie; Nettoyer

Un projet pilote pour réduire les risques d’intoxication et pour prévenir la consommation excessive (Éduc'alcool, 2023)
Montréal, le 21 avril 2023 – Éduc’alcool et le Service de police de la Ville de Montréal (SPVM) ont lancé hier le projet pilote Touche pas à mon verre* en présence du ministre de la Sécurité publique du Québec, M. François Bonnardel. Cette initiative prend la forme d’une distribution gratuite de 10 000 protège-verres afin de, notamment, […]
Keywords: Bibliographie; Dans le rapport; Nettoyer

Check tes chums - Massé, Manon (Facebook, 2023)
Keywords: Bibliographie; Nettoyer

The Morality of Musical Men: From Victorian Propriety to the Era of #MeToo - Shaver-Gleason, Linda (Lecture delivered at Utah State University, 2018)
Keywords: Bibliographie; Nettoyer

Au-delà des « vagues » #moiaussi : cinq ans de mobilisation féministe en musique au Québec (2017–2022) - Blais-Tremblay, Vanessa; Champagne, Lysandre (Intersections, 2023)
Cet article dresse le portrait de cinq organisations qui militent pour l’équité en musique au Québec depuis 2017 : MTL Women in Music, Femmes* en Musique, Lotus collective MTL Coop, shesaid.so MTL et le réseau DIG! Différences et inégalités de genre dans la musique au Québec. En s’inscrivant d’abord dans la longue lignée des travaux critiques en historiographie féministe, l’article rend compte de la pluralité des mobilisations féministes et ce, au-delà des « vagues » #moiaussi qui ont ponctué l’actualité musicale québécoise au cours des cinq dernières années (2017–2022). Dans la seconde partie, les autrices détaillent les travaux du réseau D!G , lancé en avril 2021 par Vanessa Blais-Tremblay, et présentent des retombées initiales prometteuses à la fois pour le milieu universitaire et pour les milieux de pratique en ce qui concerne l’épistémologie et les méthodologies de la « musicologie partenariale collaborative féministe ». , This article profiles five organizations that have been advocating for equity in Quebec music since 2017 : MTL Women in Music, Femmes* en Musique, Lotus collective MTL Coop, shesaid.so MTL and D!G Différences et inégalités de genre dans la musique au Québec. In line with a long tradition of critical work in feminist historiography, the authors first account for the diversity of feminist mobilizations in Quebec music beyond the #metoo “waves” which have received significant media attention over the past five years (2017–2022). In the second part, the authors detail the development of the D!G network, a feminist collaborative research partnership launched in April 2021 by Vanessa Blais-Tremblay, and its contributions to both Quebec’s music industry and to feminist partnership research epistemologies and methodologies.
Keywords: Bibliographie; Nettoyer

Accueil - Juripop (L'Aparté, 2023)
L'Aparté offre des services juridiques gratuits à toute personne ayant vécu du harcèlement dans le milieu de la culture partout au Québec
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Les femmes dans l’industrie musicale canadienne francophone - Bissonnette, Joëlle (Musicaction, 2022)
Keywords: Bibliographie; Nettoyer

Mémoire présenté à la Commission de l’économie et du travail Dans le cadre des consultations particulières et des auditions publiques sur le projet de loi n° 42 - Loi visant à prévenir et à combattre le harcèlement psychologique et la violence à caractère sexuel en milieu de travail - Juripop (2024)
Keywords: Bibliographie; Nettoyer

Workplace Sexual Harassment 30 Years on: A Review of the Literature - McDonald, Paula (International Journal of Management Reviews, 2012)
Despite its proscription in legal jurisdictions around the world, workplace sexual harassment (SH) continues to be experienced by many women and some men in a variety of organizational settings. The aims of this review article are threefold: first, with a focus on workplace SH as it pertains to management and organizations, to synthesize the accumulated state of knowledge in the field; second, to evaluate this evidence, highlighting competing perspectives; and third, to canvass areas in need of further investigation. Variously ascribed through individual (psychological or legal consciousness) frameworks, sociocultural explanations and organizational perspectives, research consistently demonstrates that, like other forms of sexual violence, individuals who experience workplace SH suffer significant psychological, health- and job-related consequences. Yet they often do not make formal complaints through internal organizational procedures or to outside bodies. Laws, structural reforms and policy initiatives have had some success in raising awareness of the problem and have shaped rules and norms in the employment context. However, there is an imperative to target further workplace actions to effectively prevent and respond to SH.
Keywords: Bibliographie; Nettoyer

Expériences de comportements sexualisés inappropriés, d’agressions sexuelles et de discrimination fondée sur le genre vécues par les travailleurs dans les provinces canadiennes, 2020 - Burczycka, Marta (Statistique Canada, 2020)
Keywords: Bibliographie; Nettoyer

3 M$ à Juripop pour venir en aide aux victimes de harcèlement et de violence dans le milieu culturel - Cabinet du ministre de la Culture et des Communications et ministre responsable de la Jeunesse (Gouvernement du Québec, 2023)
Keywords: Bibliographie; Dans le rapport; Nettoyer

L'Union des artistes dépose des griefs pour harcèlement - Radio-Canada (Radio-Canada, 2017)
Après une vague de dénonciations de gestes à caractère sexuel dans le milieu artistique, l'Union des artistes (UDA) annonce avoir déposé des griefs pour harcèlement.
Keywords: Bibliographie; Nettoyer

*Loi visant à harmoniser et à moderniser les règles relatives au statut professionnel de l'artiste - Gouvernement du Québec (LQ2022, c 20, 2022)
Keywords: Bibliographie; Nettoyer

Révision des lois sur le statut de l'artiste - Cabinet du ministre de la Culture et des Communications et ministre responsable de la Jeunesse (Gouvernement du Québec, 2022)
QUÉBEC, le 3 juin 2022 /CNW Telbec/ - L'Assemblée nationale du Québec a adopté à l'unanimité aujourd'hui le projet de loi numéro 35, Loi visant à moderniser et à harmoniser les règles relatives au statut professionnel de l'artiste, déposé par la ministre...
Keywords: Bibliographie; Nettoyer

Avantage pour membre - Assocation canadienne des humoristes stand-up, Sketch & Impro (AQHS, 2021)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Musical genius and/or nasty piece of work? Dealing with violence and sexual assault in accounts of popular music’s past - Strong, Catherine; Rush, Emma (Continuum, 2018)
For many years, the mistreatment of women in particular has essentially been normalized in many parts of the music industry. In recent years, however, there has been an increase in women coming forward and telling their stories, and asking that men be held accountable for wrongdoing. This interdisciplinary (sociology and philosophy) paper pursues two key feminist questions prompted by recent developments. Firstly: How has the construction of the history of popular music legitimated the continuation of this situation? ‘Looking back’ historically and sociologically, examples are provided of the legitimation or ignoring of violence against women (VAW) in the history of popular music to date. Secondly: How should we [archivists, historians, heritage curators and popular music educators], from now on, construct the history of popular music in a way that doesn’t legitimate VAW? Turning to ‘look forward’, applied ethics frameworks are used to explore different aspects of this second question.
Keywords: Bibliographie; Nettoyer

Theatre-making in the age of #MeToo: Working cross-culturally toward a framework for making safer creative spaces - Park, Younghee (Université de technologie du Queensland, 2022)
Keywords: Bibliographie; Nettoyer; Raphaël

For the Love of Music: Ending Sexual Harassment in the Music Industry - Musicians’ Union (2021)
Keywords: Bibliographie; Nettoyer

Raising Their Voices: Independent Review into Sexual Harm, Sexual Harassment, and Systemic Discrimination in the National Music Industry - Shehadie, Alexandra; The Review Team (Support Act, 2022)
Keywords: Bibliographie; Nettoyer

The Experiences of Canadian Women in Popular Music: “even on the worst sick no gas freezing canadian middle of january rockie mountain or halifax breakdown there is nothing better to do for a living” - MacKay, Robbie (Université Queen’s, 2008)
Keywords: Bibliographie; Nettoyer

Les dénonciations publiques d'agressions sexuelles : du mauvais usage de la présomption d’innocence - Lessard, Michaël (Revue Femmes et Droit, 2017)
French Abstract: Lorsqu’une victime dénonce son agresseur sur la place publique, certaines personnes tentent de la réduire au silence en invoquant le droit à la présomption d’innocence. Ce fut particulièrement évident en 2014, lors du mouvement #AgressionNonDénoncée ; ce le fut encore à l’automne 2015, alors que des femmes autochtones de Val-d’Or dénonçaient les agressions sexuelles commises à leur endroit par des policiers ; ce le fut aussi en 2016 à l’occasion de la dénonciation du député Gerry Sklavounos par Alice Paquet ; et l’argument légaliste réapparaît ainsi périodiquement sur la scène publique. Pourtant, peut-on vraiment bâillonner une victime en mettant de l’avant les droits de son agresseur ? L’auteur estime qu’il s’agit là d’un mauvais usage de la présomption d’innocence. Dans ce texte, il explique que la présomption d’innocence doit être replacée dans son contexte juridique. Le droit à la présomption d’innocence est un principe fondamental qui protège les accusés contre le pouvoir punitif de l’État. Il trouve uniquement application dans le processus pénal et n’est pas conçu pour être employé sur la scène publique. De plus, l’auteur explique que, dans le cadre du processus pénal, la présomption d’innocence favorise la création d’un espace de discussion où les parties peuvent débattre de la culpabilité. Pourtant, lorsqu’elle est invoquée sur la scène publique, elle ne fait que placer les victimes dans un processus violent de remise en question de leur crédibilité, tout en protégeant les agresseurs. Son invocation crée une atmosphère qui décourage les dénonciations. Le débat public dévie, laissant peu de place pour critiquer nos systèmes de plaintes dysfonctionnels et la culture du viol. En ce sens, la présomption d’innocence n’est pas invoquée afin d’établir un dialogue constructif, mais plutôt pour faire taire les critiques.English Abstract: When a victim reports her aggressor publicly, some people try to silence her voice under the guise of the right to the presumption of innocence. This was especially remarkable in 2014, within the movement #AgressionNonDénoncée; and again in the fall of 2015, when Val-d’Or Indigenous women reported being sexually assaulted by police. It was also the case in 2016 when Alice Paquet denounced Member of Provincial Parliament Gerry Sklavounos, and the legal argument thus periodically reappears on the public stage. However, can we really silence a victim by advancing the rights of her aggressor? The author believes that this is a case of inappropriate use of the presumption of innocence. In this text, he explains that the presumption of innocence must be placed in its legal context. The right to the presumption of innocence is a principle that protects litigants against the punitive power of the state. Its sole application belongs in the criminal process, and it was not designed to be used as such on the public stage. In addition, the author explains that, at the heart of the criminal process, the presumption of innocence promotes the creation of a discussion space where all parties may debate the guilt. However, when it is invoked in the public sphere, it only places the victims in an aggressive process of questioning their credibility while protecting the aggressors. Its invocation creates a climate that deters denunciations of sexual assaults. The public debate deviates, leaving little room to criticize our dysfunctional complaint systems and rape culture. In that sense, the presumption of innocence is not invoked in order to establish a constructive dialogue, but it has the effect of shutting down its critics. In this article, the author explains why the right to the presumption of innocence must not be engaged in this way in the public sphere.
Keywords: Bibliographie; Nettoyer

Accusations d’agression sexuelle et de diffamation: Jasmin Roy réplique et poursuit en diffamation Jean-François Robillard - Dussault, Lila (La Presse, 2023)
Un duel de poursuites en diffamation est en cours entre l’acteur Jasmin Roy et un homme qui l’accuse d’agression sexuelle, Jean-François Robillard. L’affaire a pris racine dans la foulée du mouvement #metoo, en 2020. Elle remonte à une soirée dans un bar d’Abitibi-Témiscamingue, 20 ans plus tôt.
Keywords: Bibliographie; Nettoyer

Une présumée victime d’agression sexuelle poursuivie en diffamation pourra rester anonyme - Marin, Stéphanie (Le Devoir, 2022)
Au coeur de la poursuite : une publication dénonçant l’humoriste Alexandre Douville sur la page Dis son nom.
Keywords: Bibliographie; Nettoyer

Comedy’s double killjoy: workers’ DIY strategies to address harassment and precarity in the comedy industry - Trusolino, Madison; Ships, Diandra (Feminist Media Studies, 2023)
Since 2017, the #MeToo movement has highlighted gender-based violence and harassment in the comedy industry, where those comedians affected have little to no workplace infrastructure to lean on. Because comedy clubs are described as venues rather than sites of work, comedy workers are not technically employees and are not protected by workplace safety laws nor supported by professional organizations or unions. We argue that the lack of a formal workplace and its related precarity exacerbates violence against women, queer, transgender, disabled, and/or workers in the Canadian and American comedy industries, pushing comedy workers to enact do-it-yourself workplace safety strategies to protect themselves and one another. We describe these protective, caring activities as akin to Brenda Parker’s “double killjoy,” and push our understanding of creative work into places of public resistance and life-making.
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Plan de lutte contre les violences et le harcèlement sexistes et sexuels dans le spectacle vivant - Ministère de la Culture français (2021)
Keywords: Bibliographie; Nettoyer; Raphaël

The Royal Court in the Wake of #MeToo - Fallow, Catriona; Mullan, Sarah Jane (Performing #MeToo: How Not to Look Away, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Encouraging Safer and More Supportive Working Practices in Theatre - Society of London Theatre; UK Theatre (2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Education in Theatrical Intimacy as Ethical Practice for University Theatre - Shawyer, Susanne; Shively, Kim (Journal of Dramatic Theory and Criticism, 2019)
Keywords: Bibliographie; Nettoyer; Raphaël; acting; ethics; pedagogy; theatre; theatrical intimacy

Masculinity after #MeToo in Mainstream Theatre - Mignon, Eloïse; Rae, Paul (Performance Research, 2019)
Keywords: #MeToo; Arthur Miller; Bibliographie; Geoffrey Rush; King Lear; Nettoyer; Raphaël; Sarah Kane; masculinity; theatre

Supporting Brave Spaces for Theatre-​Makers Post-#MeToo: A Chicago-Based Study on Rehearsing and Performing Intimacy in Theatre - Studham, Susan Fenty (Performing #MeToo: How Not to Look Away, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Krytyczki as Activists: On Theatre Criticism, Affect, Objectivism and #MeToo in Polish Drama Schools: Interview with Monika Kwaśniewska - Lech, Kasia (Critical Stages/Scènes critiques, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

We Get It: Calling Out Sexism and Harassment in Australia’s Live Performance Industry - Thomasson, Sarah (Performing #MeToo: How Not to Look Away, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Performing Arts Training in the Age of #MeToo - Spencer, Jennifer (Voice and Speech Review, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

The Change You Want to See: Results of the first-ever survey of workplace sexual harassment in the Canadian performing arts, film, and television industries - Aftermetoo (2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Analysis of the “Regional Survey on Violence and Harassment in the Workplace in the Audiovisual and Performing Arts Industry in Latin America” - FIA-LA; UNI Americas MEI (International Federation of Actors et UNI Americas MEI / Panartes, 2022)
Keywords: Bibliographie; Nettoyer; Raphaël

#MeToo: Theatre Women Share Their Stories - Heyliger, Yvette (Performing #MeToo: How Not to Look Away, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Institutional Responses to #MeToo: A Conversation - Mengesha, Weyni; Dreyer-Lude, Melanie; Clarke, Kristian; Shaw, Kathryn; Warwick, Jacqueline; Palmer, Alisa; Dubois, Frédéric (Canadian Theatre Review, 2019)
Theatre administrators, artistic directors, and heads of programs from across Canada have a conversation about how institutional policies and cultures have shifted in the wake of #MeToo. The conversation features Kristian Clarke, Executive Director of the Dancer Transition Resource Centre (DTRC); Frédéric Dubois, Director of the French Section, National Theatre School; Melanie Dreyer-Lude, Chair of the Department of Drama at the University of Alberta; Weyni Mengesha, Artistic Director of Soulpepper Theatre; Alisa Palmer, Artistic Director of the English Section, National Theatre School; Kathryn Shaw, Artistic Director of Studio 58 at Langara College; and Jacqueline Warwick, Director of the Fountain School of Performing Arts, Dalhousie University. The participants reflect on the challenges of taking stock of the impacts and effects of a cultural movement that is still unfolding and the ways in which #MeToo has changed the relationship between training institutions and the performing arts industry.
Keywords: #MeToo; Bibliographie; Nettoyer; Raphaël; intimacy coaching; performing arts industry; sexual harassment policy; theatre training

“Sorry Not Sorry”: Apologizing in the Wake of #MeToo - MacArthur, Michelle (Canadian Theatre Review, 2019)
This article explores what it means to apologize for misconduct in the #MeToo era through three examples from the Canadian theatre industry: a private apology (Randolph College for the Performing Arts), a public apology (Citadel Theatre), and an absent apology (Soulpepper Theatre). Understanding a public apology as a performative utterance meant to restore a community’s trust, this article suggests the importance of examining the paratexts generated by and around it that help it achieve its function. From policy revisions, to media interviews, to public forums, these materials and events are crucial in the meaning-making process in which a #MeToo apology is engaged, especially when the theatre community’s access to the apology itself is limited. The article concludes by situating its case studies in relation to issues of misconduct in theatre education and training institutions.
Keywords: #MeToo; #SorryNotSorry; Bibliographie; Canadian theatre; Citadel Theatre; Nettoyer; Randolph College for the Performing Arts; Raphaël; Soulpepper Theatre; public apologies

A Single Drop of Water: Vulnerability, Invisibility, and Accountability in South Korean Theatre’s Moment of Crisis - Younghee, Park; Neideck, Jeremy (Performance Paradigm, 2020)
In early 2018, encouraged by the #MeToo movement sweeping the Western media landscape, Korean actor Park Younghee took to Facebook to write of her experiences of sexual harassment at the hands of a prominent theatre director and academic in the 1990s. While Younghee didn’t publicly name her abuser, it was not long before the social media machine identified Oh Tae Suk as the man she alluded to, and his world-renowned Geukdan Mokwha as the site of her abuse. Days later, prolific theatre director Kim Soo-hee made allegations of violence and sexual abuse against Lee Yoon-taek, the artistic director of the juggernaut theatre company Yeonhuidan Georipae, setting off a firestorm in the South Korean Media that has yet to die down. In South Korea, public performances of grief, allyship, and holding the government to account are hallmarks of democratic transformation. In this article, Park Younghee tells parts of her story to longtime collaborator Jeremy Neideck, and they attempt to weave a coherent narrative out of their yearlong discussion about the social, cultural, and political histories of Korea. This article seeks to illuminate, but not necessarily explain, the environments in which men like Lee Youn-taek and Oh Tae Suk were able to perpetrate abuse.
Keywords: Bibliographie; Nettoyer; Raphaël

Mapping the Stage Differently: Theatre #MeToo Movement and Internet Culture in South Korea - Yoon, Soo Ryon (Gender IT : Feminist reflexion on Internet policie, 2019)
Keywords: Bibliographie; Nettoyer; Raphaël

Creating Space for Gender Diverse Theatre - Meredith, John; Levine, Sloth; Gender Explosion Working Group (StageSource, 2019)
Keywords: Bibliographie; Nettoyer; Raphaël

A Nonbinary Actor Prepares (for Battle) - Woodzick, K. Bylines (Theatre Topics, 2020)
Keywords: Bibliographie; Nettoyer; Raphaël

Preventing Sexual Harassment and Abuses of Power: A Code of Behaviour - Royal Court Theatre (2017)
Keywords: Bibliographie; Nettoyer; Raphaël

The power of abuse - Harvie, Jen (The Routledge Companion to Theatre and Politics, 2019)
Following revelations about sexual abuse in theatre and other entertainment industries in autumn 2017, this chapter explores the conditions which allow or
Keywords: Bibliographie; Nettoyer; Raphaël

Line Drawn Summit and Survey Report - Stone, Meg (Impact, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Sexual Harassment, Criminal Misconduct & Bullying in Australian Live Performance - Media Entertainment Arts Alliance (2017)
Keywords: Bibliographie; Nettoyer; Raphaël

Facing (and Fixing) the Problem of Sexual Harassment in Theatre - Lehman, Stefanie Maiya; Morris, Celestine (Southern Theatre, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Harassment and bullying in the theatre industry: a report - The Stage (The Stage, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Considering Queerness - Actor Training's Issues and Alternatives - LeBlanc, Jacob G. (Université du Commonwealth de Virginie, 2022)
Keywords: Bibliographie; Nettoyer; Raphaël

"for People Who Aren't Sure Who They Are, Theatre is a Great Place to Be": Narratives of Actors and their Sexual Identities - McCadden, Theodore Edward (Pennsylvania State University, 2015)
Keywords: Bibliographie; Nettoyer; Raphaël

Examining the Embodied Learning Experiences about Gender in Gay and Bisexual Male Actors - McCadden, Ted; Wright, Robin Redmon (Adult Education Research Conference, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Don't Act, Don't Tell: Discrimination Based on Gender Nonconformity in the Entertainment Industry and the Clinical Setting - O’Connell, Mark (Journal of Gay & Lesbian Mental Health, 2012)
The author describes anti-homosexual attitudes in the entertainment industry. Effeminate male actors generally have a hard time being cast, whether for gay or straight roles. Attitudes in the performing arts mirror those in society as a whole. Case reports are interspersed in the discussion to illustrate the points.
Keywords: Bibliographie; Nettoyer; Raphaël; acting; anti-gay; discrimination; gender nonconformity; homophobia; performing arts

Sexual Orientation & Gender Identity Diversity in Entertainment: Experiences & Perspectives of SAG-AFTRA Members - Badgett, M.V. Lee; Herman, Jody L. (SAG-AFTRA et The Williams Institute, 2013)
Keywords: Bibliographie; Nettoyer; Raphaël

Gay men in the performing arts: Performing sexualities within ‘gay-friendly’ work contexts - Rumens, Nick; Broomfield, John (Organization, 2014)
Building on emerging research on ‘gay-friendly’ organizations, this article examines if and how work contexts understood and experienced as ‘gay-friendly’ can be characterized as exhibiting a serious breakdown in heteronormativity. Taking the performing arts as a research setting, one that is often stereotyped as ‘gay-friendly’, and drawing on in-depth interview data with 20 gay male performers in the UK, this article examines how everyday activities and encounters involving drama school educators, casters and peers are shaped by heteronormative standards of gay male sexuality. Adopting a queer theory perspective and connecting with an emergent queer theory literature in organization studies, one concern articulated in this article is that heteronormative constructions of gay male sexualities constrain participants’ access to work; suggesting limits to the abilities and roles gay men possess and are able to play. Another concern is that when gay male sexualities become normalized in performing work contexts, they reinforce organizational heteronormativity and the heterosexual/homosexual binary upon which it relies. This study contributes towards theorizing the heteronormative dynamics of ‘gay-friendly’ places of work, arguing that gay male sexualities are performatively instituted according to localized heteronormativities which reinforce contextually contingent, restrictive heteronormative standards of gay male sexuality which performers are encouraged to embody and perform both professionally and personally.
Keywords: Bibliographie; Nettoyer; Raphaël

Irish Equity Survey 2016 - Irish Equity (2016)
Keywords: Bibliographie; Nettoyer; Raphaël

Contemporary Feminist Protest in Ireland: #MeToo in Irish Theatre - Fitzpatrick, Lisa (Irish University Review, 2020)
This essay draws upon the work of Judith Butler, Sara Ahmed, and Germaine Greer to consider the #MeToo movement and its reflection in the work of the author's students and the scandal at Dublin's G...
Keywords: #MeToo; Bibliographie; Contemporary Feminism; Intergenerational; Intersectional; Nettoyer; Raphaël; Teaching

#MeToo In Polish Theatre Education - Kwaśniewska-Mikuła, Monika (Philosophy, Sociology, Psychology and History, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Facing Sexual Harassment and Abuse in the Feminizing Museum - trivedi, nikhil; Wittman, Aletheia (Journal of Museum Education, 2018)
Despite the growing number of women in museums, the undervaluing of educational work traditionally associated with women, and labor largely done by women today, persists. This begs the question: in what other ways are women and femmes working in museums undermined despite their growing presence as workers and the emerging centrality of the educational role of museums? In society more broadly, we see how undervaluing women and their labor leads to a spectrum of treatment that can be considered violent. In this spectrum, we include pay and benefit disparities, disempowerment, and marginalization through sexist, homophobic, and transphobic comments and objectification, harassment, threats, verbal, physical, emotional, and financial abuse, and at the far end of the spectrum sexual assault and murder. In this article, we discuss data collected through a survey conducted about incidences of sexual abuse and harassment experienced by museum workers. We explore the results of the survey in relation to the gender-based division of labor and skills among the museum workforce. We look to the responses to this survey as a gauge of how much power women and gender non-conforming people have in their daily work lives in museums and propose actions that could increase empowerment and support.
Keywords: Bibliographie; Myriam; Nettoyer; Sexual violence; feminization; gender equity; labor; museum education; museum workers

Le point de vue des improvisatrices au sujet des inégalités et des stéréotypes de genre véhiculés en improvisation théâtrale et ce que ceux-ci révèlent sur la société : Une recherche en travail social féministe - Robert Durant, Catherine (Université du Québec à Montréal, 2020)
Keywords: Bibliographie; Coffre à outils; Nettoyer; Sophie-Anne

Jouer Sur le Banc Les Filles Dans le Monde de L'improvisation. - Walsh-Viau, Emmanuelle.; Joubert, Lucie (Somme Toute, 2022)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Portrait de la pratique de l'improvisation théâtrale en milieu scolaire et plan d'action pour son optimisation - Garneau, Jocelyn (L'escabeau, 2021)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Rapport de recherche sur l'état du milieu du spectacle d'improvisaiton théâtrale au Québec - Garneau, Jocelyn (Le théâtre de la Ligue Nationale d'Improvisation et la Rencontre Théâtre-Ados de Lavac avec l'appui financier du Ministère de la Culture et des Communications du Québec, 2020)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Politique de prévention et d’intervention contre l’intimidation, le harcèlement et la violence - École nationale de cirque - Montréal (2019)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

Politique visant à prévenir et à combattre les violences à caractère sexuel - École nationale de cirque - Montréal (2018)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

SPEAK OUT: together for a safer circus - Fédération européenne des écoles de cirque (FEDEC); JUMP (2023)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Violences à caractère sexuel: Les actes « graves » de Samuel Archibald - Perron, Louis-Samuel (La Presse, 2022)
L’écrivain réputé Samuel Archibald a profité de son statut de professeur de littérature pour avoir des relations sexuelles avec deux étudiantes sous son autorité, conclut une enquête indépendante commandée par l’Université du Québec à Montréal (UQAM). Une de ces femmes l’accuse même de l’avoir étranglée lors d’une relation sexuelle non consentie. Des actes « graves » et « hostiles » qui ont mené à son départ en catimini de l’UQAM l’an dernier.
Keywords: Bibliographie; Irina; Nettoyer

Montréal une ville festive pour toutes: Avis sur la sécurité des femmes et des jeunes femmes cisgenre et trans lors des événements extérieurs à Montréal - Conseil des Montréalaises (2017)
Keywords: Bibliographie; Camille; Nettoyer

Il était une fois... de trop - Institut national de l'image et du son. (2024)
Une formation pour prévenir le harcèlement en culture.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

“She’s just another pretty face:” sexual harassment of female photographers - Somerstein, Rachel (Feminist Media Studies, 2021)
This article examines sexual and gendered harassment among professional female editorial photographers, whose experiences have largely been under-researched. It draws on semi-structured interviews conducted between 2017–2019 with 17 female professional editorial photographers, aged 23–82, who work in a variety of beats. Sixteen of 17 interviewees encountered sexual harassment, with gendered harassment the most common. Harassers included professors, other photographers, colleagues, salespeople, subjects, and the general public, whom photographers encountered at school, work, while networking, and when using and buying gear. Largely, participants addressed the sexual and gendered harassment on an individual level, rather than reporting it to editors or other authorities. These findings add qualitative nuance to quantitative research that suggests physical risks and economic precarity may drive women from the profession.
Keywords: Bibliographie; Embodiment; Myriam; Nettoyer; Sexual harassment; female journalists; gender and work; photographers; photojournalism

Patriarchal pits: the gendered experiences of female concert photographers - Lough, Kyser (Journal of Gender Studies, 2020)
While the presence of women in photojournalism is increasing, the way they are treated by their male counterparts remains unbalanced. Drawing from feminist theory and embodiment, this study examines how the gendered experience plays out for women in a particular niche of photojournalism; concert photography. The restricted access of the music scene and the embodied nature of photojournalism combine to present unique barriers for women. In-depth interviews with male and female concert photographers show women still face a form of patriarchal oppression in the field. This is seen through gendered language, such as ‘one of the guys’ versus a ‘mom in the pit’, embodied actions such as direct sexual harassment or indirect benevolent sexism, and in how women are questioned when they identify themselves as a photographer.
Keywords: Bibliographie; Myriam; Nettoyer; Photojournalism; concert photography; embodiment; feminist theory

Rapport de recherche sur l’éthique en regard des violences à caractère sexuelle dans le milieu de l’humour québécois francophone - Bernier, Dominique; Paré, Christelle; Carbonneau, Karine; Vernus, Judith; Morency, Sophie-Anne (UQÀM et partenaires, 2022)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Sexual Harassment in Display Work: The Case of the Modeling Industry - Crowley, Jocelyn Elise (Gender & Society, 2021)
Keywords: Bibliographie; Cultural industries; Display work; Fashion; Informal industries; Modeling industry; Myriam; Nettoyer; Power dynamics; sexual harassment

How Independent Contractors Respond to Sexual Harassment: The Case of the Modeling Industry - Crowley, Jocelyn Elise (Employee Responsibilities and Rights Journal, 2022)
Sexual harassment continues to be a problem that most commonly affects women in the United States workforce today. While there are legal and organizational remedies available, most of these mechanisms for redress only exist for workers in traditional employeremployee contexts. Independent contractors, self-employed workers who represent a growing number of labor force participants in this economy, can therefore only use informal means of addressing sexual harassment. This study used grounded theory methods to analyze 88 separate narratives of sexual harassment from 70 fashion models, an overwhelmingly female set of independent contractors currently operating in the American economy. The aim of the analysis was to understand the mix and meaning behind the use of informal strategies—more specifically confrontation versus non-confrontation—in response to this sexual harassment. Notably, models most often confronted the perpetrators of harassment. Critically, however, those models who chose non-confrontation did not minimize the abuse that they faced. Instead, they either saw themselves as powerless or engaged in self-blame when faced with harassment on the job.
Keywords: Bibliographie; Confrontation; Fashion industry; Independent contractors; Models; Myriam; Nettoyer; Sexual harassment

Challenging gendered power: How sexual harassment perpetrators respond to victim confrontation - Crowley, Jocelyn Elise (Gender, Work & Organization, 2023)
Sexual harassment is a problem that continues to plague mostly women in the American workforce today. One tool that victims can use in these situations is confrontation, either through verbal or physical means. Yet, understudied to this point is how perpetrators respond to confrontation, which is highly salient as to whether this is an effective tool for victims. This study uses grounded theory methods to analyze 31 accounts of sexual harassment from within the fashion industry that recorded perpetrators' responses to victim confrontation to clearly unwanted, abusive behavior. I argue that specific features of the fashion industry, or a “display work culture,” embolden perpetrators to effectively thwart any type of confrontation. Indeed, this study finds that these predominantly male perpetrators of sexual harassment moved to reassert their dominant position over their female victims in the moment of confrontation, immediately after being confronted, and even later, well beyond confrontation, as they aimed to reestablish normal business practices as usual. This research thus dispels a significant sexual harassment myth that victims working within this culture are able to stop perpetrators simply by speaking up and/or fighting back and points to the need for the development of sexual harassment theory to incorporate work culture-related risk factors and remedies.
Keywords: Bibliographie; Myriam; Nettoyer; confrontation; display work culture; fashion industry; perpetrators; sexual harassment

An Examination on Sexual Harassment Activities in the South African Professional Performing Arts Industry - Yende, Sakhiseni Joseph (Journal of African Films & Diaspora Studies, 2021)
Keywords: Bibliographie; Nettoyer; Patriarchal power; Performing arts industry; Professional theatres; Raphaël; Sexual harassment; Women in theatre

Sexual Harassment in the Norwegian Theatre World - Kleppe, Bård; Røyseng, Sigrid (The Journal of Arts Management, Law, and Society, 2016)
The aim of this article is to provide insight into the phenomenon of sexual harassment in the theatre world. A survey among Norwegian actors is presented showing that sexual harassment is much more prevalent in the theatre world than in Norwegian work life in general. Further, the article aims at understanding why the prevalence is as high as it is. Based on qualitative interviews, the article points out some risk factors that shed light on the high prevalence of sexual harassment. Lastly, the risk factors are related to charismatic authority as an important power base in the theatre world.
Keywords: Art organizations; Bibliographie; Nettoyer; Raphaël; charismatic authority; gender roles; mixed methods; sexual harassment; theatre

La quatrième vague du féminisme : quel impact sur le champ littéraire ? - Mairesse, Lise (Université catholique de Louvain, 2022)
Keywords: Bibliographie; Irina; Nettoyer

Title IX, Esports, and #EToo - Stoever, Jane K (The George Washington Law Review, 2021)
As colleges and universities increasingly award video gaming scholarships, field competitive esports teams, construct esports arenas in the centers of campuses, and promote student interaction through gaming, schools should anticipate the sexual cyberviolence, harassment, and technology-enabled abuse that commonly occur through gaming.
Keywords: Bibliographie; Irina; Nettoyer

Gendered Barriers In The Gaming Industry - Singh, Tanya (Journal of Sports Law, Policy and Governance, 2020)
As of 2019, there are an estimated 2.5 billion garners globally. Roughly half of all garners are female. Despite the figures, there is a serious underrepresentation of female gainers in the professional gaming and game development community. It is thus important to examine the underlying causes hindering equally capable female gainers and game developers from pursuing a serious career in gaming, at par with their male counterparts.In this article, the authorexamines the impact of the culturalassociationof games with the male demography, stereotypes andstructuralbarrierslimiting women from realizing theirfullpotential, female representation in video games and workplace, pervasive misogyny and sexual harassment of women across all levels in the industry, and lastly, the steps that can be taken to better the status quo in favour of women.
Keywords: Bibliographie; Irina; Nettoyer

Speaking in Public: What Women Say about Working in the Video Game Industry - De Castell, Suzanne; Skardzius, Karen (Television & New Media, 2019)
Since the 1990s, conversations about the dearth of women working in the video game industry have centered on three topics: (1) ways to draw more women into the field, (2) the experiences of women working in the industry, and (3) the experiences of those who once worked in the industry but left. Although there has been considerable research on the conditions and occupational identities of video game developers, less scholarly attention has been devoted to women in gameswork, the barriers/obstacles and challenges/opportunities they face, and how they talk about their experiences. This article offers a feminist approach that demonstrates how discourse focused on affect can be reread as intimately related to silences about power and how the rhetorical constraints that public speech imposes upon what can be said about “women in games” aid us in understanding what might remain unspoken, and why.
Keywords: Bibliographie; Irina; Nettoyer

Exploring Vicarious Liability to Remedy the #E-Too Movement - Hewson, Eloise (York Law Review, 2022)
The esports, or competitive video gaming, industry is an exciting area of economic and cultural growth. Gaming can facilitate interpersonal connection, shared problem-solving, and creativity. Players may purchase a game, watch a streamer play it online, join an online gaming community, attend a tournament, compete professionally, or find employment in game development or a related field. The gaming industry generates enormous economic value and employs tens of thousands of people in the UK alone. However, the esports sector does not extend its benefits equally. Women are regularly verbally harassed in video games, countless women have been groped at esports events, women have been raped by professional players, underage fans have been groomed. Abuse is endemic to online gaming communities.
Keywords: Bibliographie; Irina; Nettoyer

Winnipeg comedy club defends decision to book Louis C.K. despite sexual misconduct - Caruk, Holly (CBC News, 2019)
An American comedian and actor who admitted to sexual misconduct will take the stage at a Winnipeg comedy club next week but not everyone is lining up for tickets.
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Politique visant à prévenir et à combattre les violences à caractère sexuel (Annexe E) - École nationale de l'humour (2021)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

ReadTheCode.ca - Canadian Creative Industries (2017)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

Pour les prochaines dénonce une culture toxique en humour - Ruel-Manseau, Audrey (La Presse, 2019)
Des humoristes de la relève affirment que le milieu de l’humour reste gangréné par la culture du viol, même deux ans après le mouvement mondial #moiaussi. En mettant sur pied Pour les prochaines, les jeunes femmes souhaitent « éradiquer » les inconduites sexuelles de l’industrie, et tendent la main aux acteurs importants du monde comique afin qu’ils s’allient pour poser des actions concrètes.
Keywords: Bibliographie; Nettoyer

Climat toxique dans le milieu de l’humour, malaises en conférence de presse - Piqueur, Lucie (Urbania, 2019)
Le regroupement « Pour les prochaines » souhaite en finir avec la culture du viol en humour, mais c'est pas gagné.
Keywords: Bibliographie; Nettoyer

#ThisIsArtSchool Is Exposing Allegations Of Racism & Sexual Abuse In Montreal Universities - Elliot, Teddy (MTL Blog, 2020)
As stories of racism and discrimination towards Black, Indigenous, and people of colour continue to dominate public discourse, more and more shocking allegations come to light about the lived experiences of systemic racism.
Keywords: Bibliographie; Nettoyer

Designing Women: Learning from Feminist Legacies and the Women-In-Games Movement - Schoemann, Sarah (Georgia Institute of Technology, 2021)
In 2019 the video games industry was rocked by a slew of high-profile sexual harassment and assault allegations that some called the #MeToo movement of the games world, but to many these revelations came as no surprise. From the 2004 EA Spouse controversy to the 2014 #Gamergate harassment campaign the games industry has long been known for harboring an at times toxic atmosphere of exploitation and discrimination. This project looks at a handful of Women-In-Games organizations that set out to change the experience of women in the industry by helping newcomers to gain high tech skills and to supporting early career professionals through mentorship and community building. Along the way, it combines the study of these Women-In-Games organizations with a years-long collaboration bringing video games to the US' oldest feminist bookstore, Charis Books & More in Atlanta, GA. Through examining the work and values of two types of organizations devoted to women's equality, one a historic feminist movement-building space and the others, contemporary interventions into the professional games and tech industry, this study asks the questions "What can the Women-In-Games movement learn from the rich history of feminist organizing at spaces like Charis?" "Can games play a part in feminist movement building?" and "What does the future of feminist organizing look like in the games industry?”
Keywords: Bibliographie; Irina; Nettoyer

Let Her Play: A report on gender-based violence in video games - Mettler, Kirsten (Embodied: The Stanford Undergraduate Journal of Feminist, Gender, and Sexuality Studies, 2022)
Globally, video games are a $152 billion industry, and approximately 3.1 billion people, or 40% of the population, are players (Ingersoll & Anti-Defamation League, 2019, Price, 2020). Gaming is a huge industry, and it’s only getting bigger. Unfortunately, women and other historically marginalized groups often face staggering levels of harassment and violence in these communities. This report aims to explore the issue of gender-based violence in video games by analyzing contributing factors and proposing gaming company interventions.
Keywords: Bibliographie; Irina; Nettoyer; esports

We protect animals well": A structural approach to abusive conduct within circus schools - Matthis, Rosa (Linköping University, 2021)
This master thesis investigates abusive conduct in circus schools. Focus is put on the management level in order to achieve and provide knowledge of measures and attitudes related to prevention. Th ...
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Les expériences des victimes de violence sexuelle dans les programmes de justice réparatrice - Wemmers, Jo-Anne; Parent, Isabelle; Casoni, Dianne; Quirion, Marika Lachance (Centre international de criminologie comparée, 2020)
Keywords: Bibliographie; Expérience; Justice; Nettoyer; Système judiciaire; Victimes; Violence

Are Female Clowns Politically Incorrect? A Case Study on Female Clowns’ Political Engagement at the 7th “Esse Monte de Mulher Palhaça” festival in Rio de Janeiro - Cézard, Zed (Cadernos de Arte e Antropologia, 2020)
By linking the notion of politics with clown practices played out during the biennial festival «Esse Monte de Mulher Palhaça» in Rio de Janeiro (2018), dedicated specifically to female clowns, the relations between politics and feminism are raised, as well as the question of the place of clowns and women within the social system in which they act. In addition to reassessing the concept of politics through this new field of application, looking at what artistic practices convey or denounce as inequalities, allows us to identify politicized and political social elements. The private sphere, the power relations, the importance of gender, and the body and sexuality as treated in the festival’s performances raise political issues. We are lead to think of the phenomenon of Brazilian female clowns as a political space of claims, in particular feminist ones, and a resistance to dominant sexist normativity.
Keywords: Bibliographie; Brazil; Nettoyer; Sophie-Anne; female clowns; feminism; activism; politics

The impact of intervention measures on sexual harassment in the film and television industry - Eng, Ben; McKinney, Ralph; Shao, Lawrence (Journal of International Management Studies, 2019)
Since 2017, increased sexual harassment incidents have been reported in Hollywood; yet, little guidance has been offered on how organizations, which are informally governed by their network members, can effectively reduce sexual harassment. Building upon the theory of network governance, this paper suggests social mechanisms, which are used to coordinate and safeguard exchanges between Hollywood organizations, are more effective at reducing incidents of workplace sexual harassment than traditional strategies. These social mechanisms direct change to the macroculture through collective sanctions that damage the perpetrators reputation and restrict access to network opportunities. In essence, perpetrators become toxic assets that Hollywood avoids and this avoidance is similar to economic sanctions that can deter sexual harassment.
Keywords: Bibliographie; Irina; Nettoyer

#TimesUp on Individual Litigation Reform: Combatting Sexual Harassment through Employee-Driven Action and Private Regulation - Dugan, Natalie (Columbia Journal of Law and Social Problems, 2020)
Keywords: Bibliographie; Irina; Nettoyer

Sexual Harassment in the Creative Industries: Tolerance, Culture and the Need for Change: Sexual harassment in the creative industries - Hennekam, Sophie; Bennett, Dawn (Gender, Work & Organization, 2017)
The economic, social and cultural contributions of the creative industries are essential elements of many societies and their governments’ policies. However, there is growing evidence that precarity, competition and lack of regulation within these industries is exacerbating inequalities with respect to gender, race and class. With a focus on gender and sexual harassment among female workers, this study involved 32 in-depth interviews with women working in the Netherlands’ creative industries. Data were analyzed using content analysis. Findings suggest that sexual harassment is prevalent, and many women considered it to be part of their occupational culture and career advancement. Four factors inﬂuenced this phenomenon: competition for work; industry culture; gendered power relations; and the importance of informal networks. Implications include the need for a climate of non-tolerance, sector-speciﬁc research and guidelines, sensitivity training and further work with unions and professional associations to provide worker protection strategies traditionally undertaken by organizations. The article concludes that effective sexual harassment prevention requires action at the individual, educational, sectoral and governmental levels, beginning with public conversations to convey the message that sexual harassment is never acceptable.
Keywords: Bibliographie; Irina; Nettoyer

Women actors, insecure work, and everyday sexism in the Canadian screen industry - Liinamaa, Saara; Rogers, Malia (Feminist Media Studies, 2022)
Acting, especially in the screen arts industry, is a job where women are subjected to pronounced and widely accepted socio-cultural aesthetic ideals within an industry that has become renowned for its tolerance for and justifications of sexism and sexualized violence. However, there is a limited amount of scholarship that examines actors and acting from a work and employment perspective. Drawing on the literature on work insecurity and gender inequities in cultural work, this article examines the screen industry from the perspective of women actors in a semi-peripheral location in Canada. This is a cohort that has managed to remain in the industry, despite high levels of attrition. Drawing on in-depth semi-structured interviews, our participants identify a range of strategies they employ (toughness, silence, humour, refusal, creative resistance) to respond to workplace sexism and gender-based constraints as they try to balance their creative agency with career sustainability. Participants emphasized that finding multiple outlets for realizing creative agency is crucial to counteracting everyday sexism and remaining in the industry.
Keywords: Bibliographie; Irina; Nettoyer; Screen industry; everyday sexism; gender and cultural work; women actors and acting

Gender then, gender now: surveying women's participation in Australian film and television industries - French, Lisa (Continuum : Journal of Media and Cultural Studies, 2014)
In the Australian audiovisual industries, women are a minority of the personnel in a large number of key creative roles and have considerably lower representation than in the Australian workforce generally. Despite the decline in their participation across several fields, the under-representation of women is not being addressed by these industries. Using findings from current research that includes a major survey of Victorian activity, this article engages with the urgent need for new approaches to thinking about the contribution and innovation of women: culturally, creatively and economically. Benchmarked against the last major study in 1992 (Cox and Laura), pivotal issues examined include barriers to progression, representation by job type and workplace/organizational cultures, along with a consideration of the current successes (relative to other areas) of women in television. Business, cultural and social arguments are made for the importance of gender equity, and an understanding of the contribution and value of women to these industries.
Keywords: Bibliographie; Irina; Nettoyer

Post Weinstein: gendered power and harassment in the media industries - Cobb, Shelley; Horeck, Tanya (Feminist Media Studies, 2018)
Keywords: #MeToo; Bibliographie; Irina; Nettoyer

The impact of #MeToo in the South African film and television industry, within a historical framework - Majiba, Ntsika (Université de l'Afrique du Sud, 2022)
The study is a history project and is concerned with tracking the impact of #MeToo in the South African Film and Television industry in South Africa. Its main premise were the findings made public by a South African organization, Sisters Working in Film and Television (SWIFT) in 2017, that found that sexual harassment in the television and film industry was not just a norm but a crisis. The core focus of the study was on the development and impact of the #MeToo movement, which entailed investigating the manner in which women reacted to the hashtag (#MeToo), the reaction of their male counterparts, as well as the reaction and actions taken by the various bodies, institutions and organisations in the Film and Television industry, which included; broadcasters and production houses alike. This study begins by giving a concise background of the movement by firstly, historicising various female-led movements and comparing and contrasting them with the rise of digital movements or digital activism. The historicisation involves a brief comparison of past and present women-led activism, as well as a brief review of other hashtags like #AmINext and #Enough, on which #MeToo has had an influence. It goes on to investigate the development of #MeToo movement and to discuss the responses of the industry and individuals to the movement. The study embarked on a data collection quest by interviewing eleven female television and film practitioners in South Africa. Their ages ranged from 20 to 55. The findings of the research revealed that female practitioners were still being harassed post #MeToo, although subtly. The lack of unity amongst women in the sector was cited as one of the reasons behind the ongoing harassment. Gender parity and equity was also still lacking in the South African television and film industry. This study emerged in the midst of activism and scholarship seeking to unravel the norms of South African sexual harassment and rape culture against women. Thus, the study focused on the changes and transformations brought about by the hashtag within the industry. With South Africa’s historical background and the current circumstances around Gender Based Violence (GBV), this study was concerned with tracking whether or not digital activism had in some way been able to aid change and transformation. In particular, this study looked at the impact of the MeToo phenomenon on the women in the industry, the extent to which it empowered them, what they began to say and how they began to act. The study also explored South Africa’s ‘rape culture’ as South Africa has been proclaimed the ‘worlds rape capital’. It reflected on the colonial rule as the perpetuation of patriarchy and male entitlement over female bodies. Patriarchy in the industry was also confirmed by the findings and through data analysis, as one of the key factors in the emergence of #MeToo in South Africa, and in the utilisation of the hashtag by women in the sector to speak up against sexual harassment.
Keywords: Bibliographie; Irina; Nettoyer

Gender Equality in British Film-making: Research, Targets, Change - Cobb, Shelley; Williams, Linda Ruth (Women in the International Film Industry: Policy, Practice and Power, 2020)
In October 2017, the British Film Institute declared that it would commit to specific targets for gender equality and diversity in key production roles on films with support from the Film Fund. This decision by the BFI to set targets, arguably, did not come just from their own diversity and inclusion goals. Activist film-makers had previously called for targets for the Film Fund, especially for women directors. This chapter will give an accounting of the current state of gender (in)equality in the UK industry by: outlining new research that has clarified the stagnant inequality in the UK film industry; articulating the key role of a network of activist groups (that include researchers, professional and campaigning bodies, exhibitors and film-makers) to bring attention to the problem; putting pressure on the film industry and public bodies; and summarising institutional responses to that pressure since 2016, with a critical analysis of the potential and limits of the BFI’s relatively recently implemented diversity and equality targets.
Keywords: Bibliographie; Irina; Nettoyer

Sexual violence and nightlife: A systematic literature review - Quigg, Zara; Bigland, Charlotte; Hughes, Karen; Duch, Mariangels; Juan, Montse (Aggression and Violent Behavior, 2020)
Preventing and responding to sexual violence in nightlife settings is increasingly of global concern. The goal of this article was to identify and summarise academic studies on nightlife-related sexual violence. Specifically, to explore the nature, extent and consequences of, or associations with nightlife-related sexual violence, and interventions to prevent and respond. Of the 61 studies identified, 29 explored or reported on the nature of nightlife-related sexual violence, 22 provided information on extent, 38 on associations, and 19 on prevention and response. The majority of studies had been implemented in the past ten years (2009–2018) and in high-income countries. The review illustrates that nightlife-related sexual violence is pervasive, with lifetime prevalence reaching over 50% amongst numerous study samples. Studies suggest that a combination of factors at an individual, relationship, and community/environmental level is associated with nightlife-related sexual violence. No studies directly explored consequences, and few studies evaluated prevention and response approaches. Globally, further research is required to understand nightlife-related sexual violence, and inform the development of prevention programmes across all but particularly low and middle-income countries. Critically, interventions aimed at preventing and responding to nightlife-related sexual violence require thorough evaluation, with findings disseminated in both lay and academic literature.
Keywords: Bars; Bibliographie; Nettoyer; Nightlife; Prevention; Rape; Sexual; Violence

Sexual harassment and violence at Australian music festivals: Reporting practices and experiences of festival attendees - Fileborn, Bianca; Wadds, Phillip; Tomsen, Stephen (Australian & New Zealand Journal of Criminology, 2020)
Despite the well-documented under-reporting of sexual violence, to date, no research has considered reporting practices within the specific context of music festivals. Drawing on 16 in-depth interviews with victim-survivors, this article examines survivors’ experiences of (non)reporting sexual violence in festival settings. We argue that while some barriers to reporting are shared across contexts, others play out in context-specific ways. Our research argues that the liberal, often transgressive culture of music festivals, combined with site-specific policing practices and spatial context, creates unique impediments to reporting with particular implications in responding to, and aiming to prevent, sexual violence at music festivals.
Keywords: Bibliographie; Camille; Nettoyer

Laughter from the Sidelines: Precarious Work in the Canadian Comedy Industry - Trusolino, Madison (Creative Industries in Canada, 2022)
Creative Industries in Canada is a foundational text that encourages students to think critically about creative industries within a Canadian context and interrogate the current state and future possibilities of the industry. While much of current creative industries literature concerns the United Kingdom, the United States, and Asia, this text captures the breadth of how Canadian industries are organized and experienced, and how they operate.This ambitious collection aims to guide students through the current landscape of Canadian creative industries through three thematic sections. “Production” collects chapters focused on how national discourses and identities are produced through creative industries and the tensions that exist between policy and media. “Participation” explores how we engage with these industries in different roles: as consumer, creator, policy-maker, and more. “Pedagogies” explores how education impacts inclusion and visibility in creative industries.Truly intersectional, Creative Industries in Canada provides students with practical industry knowledge and frameworks to explore the current state of the field and its future. With a broad application to many undergraduate programs, this text is a must-read resource for those pursuing media studies, arts management, creative and cultural industries studies, communications, and arts and humanities.
Keywords: Bibliographie; Business & Economics / Industries / Media & Communications; Nettoyer; Social Science / Media Studies; Sophie-Anne

Enquête sur le portrait sociodémographique et l’égalité homme-femme chez les créatrices et créateurs d’humour au Québec – Sommaire 2018-2: Données sur la perception de l’égalité entre les femmes et les hommes - Paré, Christelle; Brouard, François (Groupe de recherche sur l’industrie de l’humour (GRIH), SCSE/CSES, Sprott Centre for Social Enterprises / Centre Sprott pour les entreprises sociales (SCSE/CSES), Université Carleton, 2018)
Keywords: Bibliographie; Humour; Nettoyer; Sophie-Anne; Types de VACS

Louis C.K.’s time’s up time out: rereading persona post-scandal - Piper, Melanie (Celebrity Studies, 2020)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Can You Come Back from Being Cancelled? A Case Study of Podcasting, Cancel Culture, and Comedians during #MeToo - Holman, Kylie J. (University of Nebraska, 2020)
Cancel culture is a new phenomenon of public shaming, facilitated by social media. This type of public shaming is accepted due to the alleged transgression of those who are cancelled. Social understanding of cancel culture does not generally allow for redemption. Using the theoretical framework of Feminist Media Studies (Van Zoonen, 1994) and Media Framing Theory (Gitlin, 1980), this study reveals the media’s role and power in the cancelling process. This study utilized a mixed-methods approach of case study and text analysis of episodes from the pop culture and politics podcast, Keep It. The case study focused on podcast episodes pertaining to two comedians cancelled for allegations of sexual misconduct in the #MeToo era [Oct. 2017 – Present]: Aziz Ansari and Louis C.K. The study also provided comparative cases of other comedians and comedic actors who were cancelled. Findings add to our understanding of cancel culture and appropriate methods of redemption for those who are cancelled.
Keywords: #MeToo; Bibliographie; Cancel culture; Comedians; Nettoyer; Podcasting; Redemption; Sophie-Anne

Comedy in the Era of #MeToo: Masking and Unmasking Sexual Misconduct in Stand-Up Comedy - Oppliger, Patrice; Mears, Kathryn (The Dark Side of Stand-Up Comedy, 2020)
With the announcement of allegations of sexual harassment and sexual assault against beloved comedians, we ask, “Can one separate the art from the artist?” Comedians are supposed to bring audiences joy and laughter; however, this role is challenged when there is incongruity between the comic persona and the real-life misdeeds of comedians. We explore the rise of the #MeToo movement and the role of comedy in exposing as well as masking allegations against Bill Cosby, Louis C.K., Al Franken, and Aziz Ansari. Guided by disposition theory and disengagement models, findings reveal factors of race, gender, and personal relationships appear to influence comedians’ assessment of fellow comedians accused of sexual misconduct. Audience members also appear to experience moral disengagement.
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Caste, gender, and “global Indian-ness”: spaces of safety in stand-up comedy in global Mumbai - James, Aju (Feminist Media Studies, 2022)
This paper argues that stand-up comedy produces the places it uses in the city of Mumbai as “safe” for new middle-class women by excluding Dalit and working-class people who are deemed “dangerous.” Such exclusion is achieved by mobilising places and infrastructure that are built to make Mumbai a “world-class” city, a process that requires the dispossession and exploitation of the masses from which the new middle-class benefits. In the context of the sexual harassment charges that hit the stand-up comedy scene in 2018 and the responses to those charges, I posit that stand-up comedy is a site where “appropriate” gender hierarchies are formulated in the pursuit of “global Indian-ness.”
Keywords: Bibliographie; Global Indian-ness; Mumbai; Nettoyer; Sophie-Anne; sexual harassment; stand-up comedy; world-class city

Sexual Violence and Gender Equality in Grassroots Music Venues: How to Facilitate Change - Hill, Rosemary Lucy; Megson, Molly (IASPM Journal, 2020)
Sexual violence in the music industry is known to impact negatively on women’s participation. We examine how grassroots venues and promoters can implement changes to tackle sexual violence and work towards gender equality. We draw on UK-based, impact-focused research which sought to raise awareness of sexual violence, and to facilitate anti-violence changes within organisations. We find that working across a city’s music scene and engaging with oversight organisations such as local authorities can aid in persuading venues and promoters to seek training. However, for individuals leading on changes, personal experiences of sexual violence as a victim/survivor or bystander are important factors in their decision. We conclude that men in the music industry need to become more aware of the need for change, and willing to act on that awareness; and that more women need to own, manage, and run venues and events.
Keywords: Bibliographie; Gender; Nettoyer; live music; music industry; music venues; prevention; sexual violence

Resilience & Melancholy: Pop Music, Feminism, Neoliberalism - James, Robin (John Hunt Publishing, 2015)
When most people think that “little girls should be seen and not heard,” a noisy, riotous scream can be revolutionary. But that’s not the case anymore. (Cis/Het/White) Girls aren’t supposed to be virginal, passive objects, but Poly-Styrene-like sirens who scream back in spectacularly noisy and transgressive ways as they “Lean In.” Resilience is the new, neoliberal feminine ideal: real women overcome all the objectification and silencing that impeded their foremothers. Resilience discourse incites noisy damage, like screams, so that it can be recycled for a profit. It turns the crises posed by avant-garde noise, feminist critique, and black aesthetics into opportunities for strengthening the vitality of multi-racial white supremacist patriarchy (MRWaSP). Reading contemporary pop music – Lady Gaga, Beyonce, Calvin Harris – with and against political philosophers like Michel Foucault, feminists like Patricia Hill Collins, and media theorists like Steven Shaviro, /Resilience & Melancholy/ shows how resilience discourse manifests in both pop music and in feminist politics. In particular, it argues that resilient femininity is a post-feminist strategy for producing post-race white supremacy. Resilience discourse allows women to “Lean In” to MRWaSP privilege because their overcoming and leaning-in actively produce blackness as exception, as pathology, as death. The book also considers alternatives to resilience found in the work of Beyonce, Rihanna, and Atari Teenage Riot. Updating Freud, James calls these pathological, diseased iterations of resilience “melancholy.” Melancholy makes resilience unprofitable, that is, incapable of generating enough surplus value to keep MRWaSP capitalism healthy. Investing in the things that resilience discourse renders exceptional, melancholic siren songs like Rihanna’s “Diamonds” steer us off course, away from resilient “life” and into the death.
Keywords: Bibliographie; Music / History & Criticism; Nettoyer; Philosophy / Social